Accurate prediction of wheat grain protein content via integration of genomic prediction and high-throughput phenotyping in breeding fields - Guoliang Wan; Lei Li; Luping Fu; Jixin Li; Boyang Xue; Shaolin Yan; Kai Wang; Zhiqiang Tao; Yonggui Xiao (Computers and Electronics in Agriculture, 2026)

Selective adsorption of biodegradable polymaleic acid for regulating the wettability difference at the fine coal–kaolinite interface - Wei Xiao; Yuping Fan; Xianshu Dong; Xiaomin Ma; Yuanpeng Fu; Yanze Mu; Maoqing Yang; Pengcheng Wen; Kangpei Jin; Dehao Li (Minerals Engineering, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Experimental investigation on the heat transfer characteristics in a vertical upward wire-wrapped tight lattice bundle with buoyancy effects - Junsen Fu; Junlong Li; Lerui Zhang; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Petrogenesis of the middle Jurassic Luorong syenite and Xishan A-type granite in the southern Qin-Hang belt, South China: Implications for contrasting mixed sources and divergent differentiation pathways - Zheng-Wei Qin; Xi-Yao Li; Wolfgang Siebel; Jian-Ming Fu; Sanzhong Li; You-Yue Lu; Yu-Xiao Yao; Yu-Shuai Yu; Bo Bao (Journal of Asian Earth Sciences, 2026)

Mannose modified soy peptide aggregates as a delivery system for vitexin: Enhancing stability and macrophage-targeted anti-inflammatory efficacy - Qianqian Wang; Yue Zhang; Zirui Xu; Yingwu Su; Xinyu Fu; Xiao Guan; Sen Li (Food Research International, 2026)

A synergistic enzymatic strategy for comprehensive improvement of bread quality and digestibility using a novel maltohexaose-forming amylase and a 4,6-α-glucanotransferase - Yu-chuan Wang; Hong Liu; Li-xiao Fu; Meng-jun Han; Qiao-juan Yan; Zheng-qiang Jiang; Yan-xiao Li (Food Hydrocolloids, 2026)

Infectious spleen and kidney necrosis virus promotes replication organelle formation and sphingolipid biosynthesis to facilitate viral replication - Wenwen Xiao; Xiaozhe Fu; Yilin Zhu; Qiquan Liu; Qiang Lin; Hongru Liang; Xia Luo; Yinjie Niu; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Reshaping of extracellular polymeric substance scaffolds, microbiota and metabolism mitigates bio-clogging in microbial fuel cell-coupled constructed wetlands - Qinghua Wang; Jiao Yin; Xuewei Fu; Lei Cheng; Xinyue Wu; Xiaofang Li; Haowei Guo; Jun Xiao; Lei Huang (Bioresource Technology, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Duplication and divergence: Two new Dmrt1 gene paralogs identified in autotetraploid Carassius auratus - Qian Xiao; Qingwen Xiao; Xu Huang; Yanlin Fu; Yuhan Yang; Chongqing Wang; Xiaowei Xu; Xidan Xu; Kun Zhang; Yue Zhou; Jinhai Bai; Zhengkun Liu; et al. (Aquaculture, 2026)

Immunogenicity and post-challenge virological outcomes of a multivalent subunit vaccine in sheep challenged with cytopathic BVDV-1a - Zhiran Shao; Jing Yuan; Yuhao Li; Lu Xiao; Rongrong Ni; Yinuo Li; Yalin Gao; Zeyao Wang; Yuting Zhang; Aodi Wu; Maoyuan Gu; Junyuan Li; et al. (Veterinary Microbiology, 2026)

Multi-endpoint in vitro toxicity profiling of heated tobacco products versus e-cigarettes under air-liquid interface exposure - Hongjuan Wang; Yushan Tian; Shigang Li; Peizhen Li; Ningning Geng; Xiao Li; Lili Cui; Yaning Fu; Shulei Han; Huan Chen; Hongwei Hou (Toxicology in Vitro, 2026)

Neoarchean prolonged subduction-related magmatism and multistage metamorphism in the Zunhua area: implications for the cratonization of the eastern North China Craton - Li-Fu Zhao; Xiao-lei Wang (Precambrian Research, 2026)

Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Dynamics of global CO2 and PM2.5 nexus and suggestions on the pathway heading to sustainable development for different income countries - Jiaxin Liu; Ben Fu; Lijian Han; Guixiang Jin; Yuhui Xiao; Keqing Chen; Weifeng Li; Weiqi Zhou; Yuguo Qian (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Analytical modeling for uplift resistance of subsea pipelines in loose sand: Local flow-around failure mechanism and smooth-pipe validation - Xiao-Mi Li; Yu-Min Shi; Ning Wang; Xiao-Bing Lu; Fu-Ping Gao (Ocean Engineering, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Divergent seasonal dynamics of high-resolution phosphorus speciation in sediment porewater of small estuaries - Yeran Yin; Hanchang Zhou; Yurui Li; Zheng Wang; Kai Xiao; Zhanrong Guo; Feng Pan; Bojie Fu (Journal of Hydrology, 2026)

An integrated multiscale air quality modelling framework for industrial park pollution: Linking local emissions to regional transport - Tao Wang; Jie Li; Joshua S. Fu; Wei Wang; Bing Liu; Bin Zhao; Yibo Zhang; Jinxiu Pan; Feng Sun; Xiu’e Shen; Zhe Wang; Xiao Tang; et al. (Journal of Environmental Sciences, 2026)

Fusion of hyperspectral and multisource remote sensing data using intelligent optimized ensemble learning to estimate the SOC content of seven mangrove species in China - Jun Sun; Weiguo Jiang; Ziyan Ling; Peng Hou; Zhijie Xiao; Zhe Yang; Ze Zhang; Bolin Fu; Lu Liu; Yuyang Li; Xu He (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

A swelling-triggered epoxy-polyethyleneimine capsule for autonomous corrosion control and synchronous multi-pollutant sequestration in harsh effluents - Xupeng Li; Zhikun Wang; Jiaqi Feng; Siyu Liu; Zixiao Chen; Qi Wang; Peiwen Xiao; Miantuo Li; Huiling Su; Jingyue Wang; Yu Fu; Songqing Hu (Chemical Engineering Journal, 2026)

Divergent controls of climate and chemical traits on the decomposition of leaf litter, fine roots, and coarse roots: a global synthesis - Xiaoxiang Zhao; Qiuxiang Tian; Siying Gong; Anders Michelsen; Li Xiao; Lihua Fu; Yan Yang; Rudong Zhao; Liang Chen; Feng Liu (CATENA, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Data-driven characterization of spatio-temporal correlations between AC terminals and occupied zones for zone-based control in large built environments - Jing Zhang; Zixuan Wang; Tianyou Ma; Hanbei Zhang; Kan Xu; Ao Li; Maomao Hu; Fu Xiao (Building and Environment, 2026)

Drivers of air pollutant and greenhouse gas emissions since 2010 in Greater Bay Area, China - Jie Li; Yuhang Xie; Zhijiong Huang; Junyu Zheng; Xiao Fu (Atmospheric Environment, 2026)

Iron-regulated crystallization in sensible-heat-driven glass-ceramics from molten lead-zinc smelting slag: Process-structure-property coupling and LCA quantification - Yibo Yang; Yusheng Tang; Hanguang Fu; Mengchen Xiao; Meichen Pan; Jixian Wu; Zhichuan Li; Zhe Tan; Zhixue Qu; Dean Pan; Xiaoguang Zhang (Process Safety and Environmental Protection, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

CIDA: A context-informed decoupling approach for soil trace element estimation using spaceborne cross-sensor data - Yishan Sun; Dan Li; Hao Jiang; Kai Jia; Shuisen Chen; Chongyang Wang; Xingda Chen; Jing Zhang; Jinyue Chen; Xiao Zhang; Wenlin Fu; Weibin Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Ultra-high pressure-assisted enzymatic extraction enhances phenolic release and functional potency in fermented dark tea extracts - Xiaoying Lin; Jun Li; Yuanshan Yu; Dengwen Lei; Tenggen Hu; Manqin Fu; Qiang Xiao; Junying Zou; Ya Gao; Chao Huang; Jing Wen (Food Research International, 2026)

Constructing amorphous-crystalline FeS via coordination regulation of ethylenediamine for efficient Cr(VI) removal from groundwater - Xuan Fu; Danqing Liu; Kelin Zhang; Yuan Feng; Xiao Zhou; Qirui Guo; Yilian Li (Environmental Research, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Highly charged nanocellulose enables triple-function hydrogels for bionic electronic skins - Danning Fu; Jiawen Wu; Huiming Xiao; Yonghao Ni; Zhixin Jia; Wanqing Wang; Lin Li (Chemical Engineering Journal, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Crop rotations modulate chemical transformation of dissolved organic matter during mineral surface-bound Fe(II) oxidation in paddy soils - Cong Wu; Fangling Li; Taoyuan Ouyang; Wei Peng; Yanqi Xiao; Fu Liu; Qihong Zhu; Na Zhang; Hao-Jie Cui; Wenjuan Liao (Applied Geochemistry, 2026)

Quality comparison between induced Qi-Nan agarwood by fungus and wild Qi-Nan agarwood - Guangyi Xiao; Yunlin Fu; Yingjian Li; Mengji Qiao; Penglian Wei (Journal of Plant Biochemistry and Biotechnology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

Bionic titanium nitride/silica nanofiber-based aerogels enabling highly efficient and stable solar-water desalination with good salt resistance - Qiuxia Fu; Wenzhe Li; Yuxin Ma; Xiangxiang Gu; Siyuan Xiao; Haoru Shan (Chemical Engineering Journal, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

Refractory Dermatophytosis Caused by Trichophyton indotineae: A Case Series Highlighting Antifungal Resistance and Management Challenges - Yubo Ma; Rong Yan; Yakun Shao; Chunying Xiao; Tianshuo Zhao; Xingyu Li; Gang Wang; Chunying Li; Yinggai Song; Meng Fu; Yanyang Guo (Mycopathologia, 2026)

From biomarkers to the risk index: a novel integrated model using multidimensional urinary biomarkers to quantify e-cigarette exposure - Lili Cui; Shulei Han; Pengpeng Yu; Ruijuan Miao; Xingfang Cun; Yuan Zhang; Peipei Ren; Pengxia Feng; Lingxiao Song; Yaning Fu; Hongjuan Wang; Yushan Tian; et al. (Archives of Toxicology, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

Immune cells in liver transplantation: Dual roles, mechanistic insights, and targeted therapeutic strategies - Yuanzhen Guo; Luoyang Wang; Wei Li; Xiaoli Liu; Jie Liang; Meiying Song; Xiao Wang; Yi Liu; Zhen Li; Shuai Li; Ningjing Fu; Jingzhen Cai; et al. (Immunologic Research, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

A spider-inspired superhydrophobic tactile sensor with machine learning-enabled slip detection for damage-free robotic fruit grasping - Zhen Wei; Chunjiang Zhao; Yuehua Huang; Siqi Li; Xinglan Fu; Chuanke Yang; Zhengwei Xiao; Guanglin Li (Computers and Electronics in Agriculture, 2026)

Late Quaternary palaeoenvironmental changes in the desert-oasis transitional area modulated by multiple forcings: Chronostratigraphic records from the Gurbantunggut Desert, NW China - Haoran Zong; Jingjing Chen; Deguo Zhang; Yujie Guo; Zihan Yan; Zaijun Li; Xiaoping Yang; Xiao Fu (Global and Planetary Change, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Global lactylation is downregulated despite lactate accumulation: lactylome data and functional insights during ISKNV infection - Zhourui Sun; Yinjie Niu; Xiaozhe Fu; Qiang Lin; Xianglin Cao; Hongru Liang; Xia Luo; Baofu Ma; Wenwen Xiao; Ningqiu Li; Jianjun Chen (Fish & Shellfish Immunology, 2026)

A critical review on whether reducing the bandgap width is the sole approach to enhancing photocatalytic efficiency in g-C3N4-based materials - Yujie Jiao; Yang Liu; Guotao Xiao; Binyuan Li; Guangjie Liu; Jiali Lei; Qikai Liu; Shengyun Fu; Yin Luo; Sujin Lu; Yaqi Mao (Environmental Research, 2026)

Double burden: Synergistic effects of menopause and obesity on high paraben exposure-induced relative androgen predominance in women - Chao Yu; Gulijiazi Yeerkenbieke; Jianping Qian; Zhenghao Wu; Wei Yao; Jian Xiao; Jie Chen; Jianfa Gao; Xiaofang Fu; Xiqing Li (Environmental Pollution, 2026)

Punicalagin alleviates enterotoxigenic Escherichia coli-induced intestinal mucosal injury via Krüppel-like factor 4 - Xiang-Guang Li; Xiaowen Zhao; Peizhi Zhu; Jibin Fu; Jiaxin Zhang; Zhixin Yu; Runting Chen; Mingxia Chen; Chuqiao Xiao; Junxia Zheng (Chemico-Biological Interactions, 2026)

Maximum mean discrepancy enhanced Informer for accurate cross-domain dual-timescale effluent prediction in wastewater treatment plants - Jun-Hong Zhou; Yang-Guang Xia; Xiao-Li Yang; Xin-Yi Xiang; Yu-Jia Fu (Bioresource Technology, 2026)

Synergistic inhibition and microbial adaptation in anammox systems under long-term salinity and fulvic acid stress - Wenjun Yin; Yilin Li; Aodong Pan; Junwei Wu; Xiaomei Su; Xiao Xiao; Feng Dong; Liang Xu; Chongjun Chen; Hailu Fu; Faqian Sun (Bioresource Technology, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Balancing accessibility, equity, and sustainability in public facility location-allocation: A Bi-level multi-objective approach - Yongqi Zhang; Xiao Fu; Dong Ngoduy; Xudong Li; Guonian Lü (Applied Geography, 2026)

Optimisation and bioactivity evaluation of Brassica rapa L. seed oil extraction using novel green dimethyl ether extraction - Wan Xiao-Fu; Yimuranjiang Subuhati; He Tian; Miao-Miao Wang; Jia-Xin Yang; Le Pan; Mu-Chun Li (Natural Product Research, 2026)

Light-driven community assembly and functional performance of aeration-free filamentous algae–partial nitrification/anammox granule - Cui-Zhong Chen; Hui-Min Fu; Tong-Xu Li; Xiao-Yu Gao; Qing Hu; Peng Yan; Jin-Song Guo; Xiao-Wei Xu; You-Peng Chen (Water Research, 2026)

A comparative study on the developmental toxicity of three dihydroxynaphthalene positional isomers in zebrafish embryos - Zijian Li; Ke Xu; Ziang Wang; Wenhui Zhi; Die Fu; Xiying Zhou; Weitao Hu; Zhonghao Xiao; Zigang Cao; Huimin Li; Xiaowen Shi (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Dual repression of OsSnRK1β1A by the deubiquitinase OsOTUB1 orchestrates energy metabolism and grain yield in rice - Ludan Zhang; Pengfei Wang; Yue Li; Shuang Yang; Yan Chen; Zhiying Ma; Jing Pan; Xiaoyu Wang; Chenyan Wang; Haoyuan An; Yuqing Xu; Yifei Xiao; et al. (Molecular Plant, 2026)

Natural water constituents boost pollutant removal in the O3/PAA system via Cu-doped LaFeO3 perovskite and in-situ formed metal complexes - Zhenyang Xu; Shuhan Fu; Zijing Ling; Shouling Li; Fengling Pan; Ning Xiao; Shuguang Wang; Tingting Zhang (Journal of Environmental Chemical Engineering, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Garnet’s impact on the petrogenesis of Himalayan leucogranites - Dong-Yong Li; Fang-Zhen Teng; Yilin Xiao; Zhi-Chao Liu; Hai-Ou Gu; Wang-Ye Li; Xiao-Chi Liu; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Quantifying scale effects in pile scour depth prediction for field applications via interpretable machine learning - Yang-Xin Zhou; Qing-Kai Song; Wen-Gang Qi; Li-Jing Yang; Xiao-Bing Lu; Fu-Ping Gao (Coastal Engineering, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

From Adaptation to Collapse: Immune Remodeling, Mitochondrial Dysfunction, and Cell Death Induced by Polystyrene Nanoplastics in Procambarus clarkii Hepatopancreas - Shengyan Pu; Han Mingming; Yi Juin Tay; Xiao Qing; Fu Hongmei; Wang Yiting; Li Zhenchao; Zhang Jingyou; Anisah Lee Binti Abdullah; Ji Liang (Marine Biotechnology, 2026)

LSTA-Swin: a long- and short-term aggregated spatio-temporal neural network for enhanced ENSO forecasting - Wei Fang; Xiao-Zhi Zhang; Yijing Li; Zhang-Jie Fu; Hai-Yan Fu (Climate Dynamics, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

Assessment and simulation of carbon storage in high-groundwater coal basins based on detailed water body classification: a case study of the Yanzhou Coalfield, China - Yanan He; Yanhua Fu; Li Wang; Wenqi Chen; Wu Xiao; Yichen Shi; Zhengshan Ju (Environmental Monitoring and Assessment, 2026)

Numerical study on the protective effectiveness of solidified soil protection layer (SSPL) for scour control of offshore pile foundations - Sheng-bang Liu; Ji-fu Yin; Jin-jian Chen; Xiao-ni Wu; Peng-xiang Li (Ocean Engineering, 2026)

Gallic acid-mediated semiquinone radicals drive a self-sustaining fenton-like system for PAH remediation in contaminated soil - Ying-Ying Wu; Xiao-Hong Ma; Song Yang; Li-Bang Ma; Fu-Zheng Zhao; Jing Sun (Journal of Hazardous Materials, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Strain-induced optical degradation on thermal performance of radiative cooling-coated PVC membrane - Junting Xiang; Jianhui Hu; Zhi Zheng; Yuke Li; Jian Lu; Wujun Chen; Paolo Beccarelli; Xiao Xue; Jingyu Zhang; Yang Fu; Saishuai Huang; Yi Xu (Energy and Buildings, 2026)

Tarsus-enriched chemosensory proteins in Achelura yunnanensis (Lepidoptera, Zygaenidae) and their interactions with pesticides - Fu-Peng Li; Zi-Hui Liu; Xiao-Rong Xiong; Jin-Lan Zhang; Hai-Yan Xiao; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2026)

Insights into microscopic mechanisms of quaternary ammonium rosin-based amide resin in removing hexose alkaline degradation pigments - Xiao-Song Tang; Wei Wei; Yan-Hong Wei; Yu-Huan Lu; Xiang-Yi Tang; Wen Li; Fu-Hou Lei (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

A comprehensive review on wine authentication and traceability: Current issues, solutions and future perspectives - Hai-Qing Qiang; Hui-Wen Gu; Xiao-Li Yin; Zhan Meng; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2026)

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Three-dimensional network binder achieves strong adhesion and rapid lithium-ion transport for practical Si/C composite electrode - Bowen Chang; Yuan Xiao; Tianmin Wang; Mengjia Wang; Mingui Li; Fu-Ming Wang; Qunjie Xu; Qiaoxia Li (Chemical Engineering Journal, 2026)

Stromal reprogramming-primed nanofiber enhances immune activation for melanoma suppression - Mingyang Li; Junhao Liang; Linhan Ding; Wenjing Dong; Rongrong Li; Baotong Xu; Yuhan Lian; Yuhan Cui; Dongsheng Zhang; Guangyi Liu; Yulin Zhang; Xiao Fu (Chemical Engineering Journal, 2026)

A structural-preserving and scalable EBI strategy for functional cellulose copolymer films - Zhining Li; Liqin Yu; Shiqiang Zhao; Zhen Ma; Kai Fu; Haoyu Li; Haolong Zhang; Xiao Li; Yi Fan; Chun Chang (Chemical Engineering Journal, 2026)

Multi-omics dissection of procyanidin C1-driven microbiota-linked EPA-enriched phosphatidylcholine signaling in multi-tissue insulin resistance - Zhihao Liu; Qihao Li; Fu Zhao; Dapeng Zhang; Xinyue Li; Daozheng Fang; Haimeng Li; Qixiang Shang; Fengyan Chen; Zhiyuan Zhen; Yong Zhu; Chang-An Geng; et al. (Chemical Engineering Journal, 2026)

Chlorine–mediated enhancement of coastal ozone pollution under long–range transport in eastern China - Zhihao Yang; Jie Li; Yuchen Liu; Jing Chen; Xiao Fu (Atmospheric Environment, 2026)

Human Amniotic Mesenchymal Stromal Cells Promote Bone Regeneration via Regulating Ameloblastoma-Derived-Bone Marrow Mesenchymal Cells Crosstalk and Autophagy in Ameloblastoma Microenvironment - Yuhuan Xiao; Xiaofeng Fu; Weina Zhou; Jin Li; Bin Yan; Fei Jiang (Tissue Engineering and Regenerative Medicine, 2026)
Background: Growing evidence validates the vital function of mesenchymal stem cells (MSCs) in tumor development. Our previous findings have illustrated the role of MSCs in the invasion and recurrence of ameloblastoma. Stem cells can be transplanted to release paracrine factors in the tumor microenvironment (TME) to inhibit tumor progression and recurrence. The paracrine function of human amniotic mesenchymal stromal cells (HAMSCs) benefits bone regeneration. However, the dual function of HAMSCs in inhibiting tumor progression and promoting bone regeneration in the TME remains unknown. Methods: To analyze the role of HAMSCS in the cross-talk between mesenchymal ameloblastoma-derived cells (M-AMCs), human bone marrow mesenchymal stem cells (HBMSCs), and HAMSCs, an in vitro co-culture system of M-AMCs, HBMSCS, and HAMSCS was prepared. An in vivo ectopic transplantation model was employed further to detect the therapeutic effect of HAMSCs on bone regeneration. Results: A high-level basal autophagy was detected in the stroma of ameloblastoma. In the in vitro co-culture models, M-AMCs suppressed the proliferation, differentiation, migration, and autophagy of HBMSCs, and conversely, HBMSCs promoted the above phenotypes of M-AMCs. HAMSCs promoted the proliferation, differentiation, migration and autophagy of the co-cultured HBMSCs. Additionally, HAMSCs mediated the cross-talk between M-AMCs and HBMSCs. The in vivo ectopic transplantation model indicated that transplanted HAMSCs promoted bone regeneration by inhibiting the growth of M-AMCs and enhancing autophagy, as well as osteogenesis in bone defects of mice. Conclusions: The interaction of M-AMCs and HBMSCs may be associated with ameloblastoma recurrence. HAMSCs regulate the cross-talk between M-AMCs and HBMSCs to increase the autophagic level in the TME, thus inhibiting the progression and recurrence of ameloblastoma and promoting bone regeneration. Therefore, HAMSC-based therapy provides an alternative to facilitate bone regeneration and repair of ameloblastoma-induced bone defects.

Tubuloside B Alleviates Aβ25-35 Induced PC12 Cell Injury by Attenuating Pyroptosis, Apoptosis and Excessive Autophagy - Hao Yang; Rao Fu; Yueyang Duan; Yongjiao Hua; Tianyu Wei; Guiping Li; Xinru Gu; Ming Li; Xiao Yu; Liang Li; Liang Cao; Zhen-zhong Wang; et al. (Neurotoxicity Research, 2026)

Unpacking asthma risks: A multi-level spatial analysis of social determinants of health in the U.S. - Ming Yan; Cong Fu; Xiao Huang; Siqin Wang; Yuchen Li; Lambed Tatah; Rui Zhu; Yanqing Xu (Applied Geography, 2026)

A spectral-physiological feature fusion model for the early detection of anthracnose in citrus leaves - Zhengwei Xiao; Chuanke Yang; Zhen Wei; Xinglan Fu; Chunjiang Zhao; Guanglin Li (Computers and Electronics in Agriculture, 2026)

Non-invasive early sex identification of hybrid sturgeon (Huso dauricus♀ × Acipenser schrenckii♂) based on multi-view images - He Gao; Qiaokun Liu; Xiao Chen; Rongzhu Zhou; Shanzhong Zhang; Junting Li; Yinhua Zhou; Suxing Fu; Chengjiang He; Tonghan Wu; Siyu Duan; Jia Xu; et al. (Aquaculture, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

Multi-satellite derived data reveals spatiotemporal dynamics of carbon-water coupling and its drivers in tropical ecosystems - Xiang Wang; Zheng Fu; Philippe Ciais; Josep Peñuelas; Jingfeng Xiao; Xing Li; Xiangzhong Luo; Chi Chen; Haoyu Xia; Tao Zhou; Paul C. Stoy; Julia K. Green; et al. (Remote Sensing of Environment, 2026)

Herbicidal activity mechanism and ecotoxicological study of novel triazolinone PPO inhibitors based on plant-derived allelochemical cinnamic acid - Li-Xia Zhao; Xian-Da Guo; Jia-Xiao Li; Yue-Li Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Comprehensive diversity index for microplastics provides insight into lake pollution sources - Yuan Zhao; Yi Yu; Yidan Gai; Xiutong Xiao; Yuxin Fu; Ziyi Nie; Mei Feng; Renjun Wang; Changchao Li; Yandong Gan; Ying Liu (Journal of Hydrology, 2026)

Distribution and enrichment characteristics of carbonate-hosted clay-type lithium resources in western Guangxi, South China - Jiarong Li; Yazhou Fu; Jiafei Xiao; Huawen Qi; Jiantang Peng; Jian Zhang (Journal of Asian Earth Sciences, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Tough, electron-ion conductive, and anti-freezing cellulose nanofiber reinforced hydrogels inspired by honeycomb as flexible wearable sensors for intelligent human health monitoring - Zhengshen Guo; Min Wang; Tong Li; Shengling Xiao; Manyu Zhou; Yuhang Li; Changlei Xia; Chunxia Chen; Qiliang Fu; Quanliang Wang; Shuangfei Wang (Chemical Engineering Journal, 2026)

Hydraulic retention time extension and multi-point reflux promote full-scale partial mainstream anaerobic ammonium oxidation (Anammox) at low temperatures - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Wen-Bo Liang; Yu-Jia Fu (Chemical Engineering Journal, 2026)

Investigating the effect of microbial inoculation on raindrop splash erosion: Indoor simulated rainfall and Hairsine-Rose model analysis - Zhaoxing Xiao; Tianxiao Li; Qiang Fu; Renjie Hou; Mo Li; Dong Liu; Fanying Kong; Qingyuan Liu; Guoqing Li (CATENA, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Characteristics and expression of the BES1 transcription factors family in foxtail millet (Setaria italica) reveal its potential roles in drought stress responses - Xueyan Xia; Xiaohong Fu; Yu Zhao; Jihan Cui; Nuoya Xiao; Meihong Huang; Yiwei Lu; Jingxin Wang; Cheng Chu; Shunguo Li; Mingwei Ding (Cereal Research Communications, 2026)

Research on Intelligent Identification of Dike Hidden Hazards Based on GprMax Forward Modeling and YOLOv11 Deep Learning: A Case Study of Wenzaobang River in Shanghai - Fu-yu Jiang; Run Han; Li-kun Gao; Jiong Ni; Jun-kai Yu; Xiao-yu Xu (Applied Geophysics, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Silica reversal reveals the lithium super-enrichment during the extreme differentiation of granitic magmas - Chun-Li Guo; Roberto F. Weinberg; Fu-Yuan Wu; Jun-Xing Zhao; Xiao-Chi Liu; Bin-Wu Zhang (Lithos, 2026)

Golden coloration of Ginkgo biloba can be driven by fine-tuning of pigment, flavonoid, and terpene metabolism - Yibin Lu; Guolin Wang; Dong Yang; Cuiping Zhang; Guo He; Xiao Zhou; Yu Liu; Weiqi Li; Chunxiang Fu; Mengzhu Lu; Gongke Zhou; Jie Meng (Journal of Plant Physiology, 2026)

UCO provides greater carbon reduction potential than plant oils across diverse biodiesel production technologies - Yang Li; Fang Wang; Xiao Fu; Ye Wu (Journal of Cleaner Production, 2026)

Eco-friendly flotation separation of molybdenite from chalcopyrite using thiotriazinone as a novel selective depressant - Mengyang Li; Xiao Wei; Ruixing Fu; Hao Lai; Shaojun Bai; Peilun Shen; Dianwen Liu; Jian Liu (Journal of Environmental Chemical Engineering, 2026)

Effectiveness of humic-acid-based composite amendments in mitigating soil cracking and erosion in cold black soil regions under climate variability - Xu Leng; Qiang Fu; Tianxiao Li; Di Wu; Xuechen Yang; Zhaoxing Xiao; Mo Li; Renjie Hou (Journal of Environmental Management, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Impact of deposition morphology on critical heat flux during pool boiling from horizontal tubes - Xiaowen Wang; Maolong Liu; Junlong Li; Junsen Fu; Xu Yan; Hongkang Tian; Tenlong Cong; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2026)

Study on the effect of high temperature on the seismic performance and rotor dynamic characteristics of the molten salt pump for reactor - Xing-Chao Shen; Yuan Fu; Jian-Yu Zhang; Jin Yang; Xiao-Yan Wang; Zhi-Jun Li (Annals of Nuclear Energy, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Integration of transcriptomic and metabolomic data reveals the low temperature response gene regulatory network of germination in soybean (Glycine max L.) - Wenhui Fu; Jingying Nie; Junli Ou; Yuchen Liu; Benshi Zhou; Yan Jing; Yonggang Zhou; Junlong Gao; Keheng Xu; Chen Feng; Hongtao Gao; Yaxin Li; et al. (Plant Science, 2026)

Nor-halimane and spiro-labdane diterpenoids with anti-inflammatory activity from Leucas ciliata Benth - Jia-Cai Kuang; Fu-Ling Cen; Xuan Zhang; Xu-Hua Nong; Xue-Ming Zhou; Xiao-Bao Li; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2026)

Peniterretonins A-D, terretonin-type meroterpenoids from the marine-derived fungus Penicillium simplicissimum - Yanan Yang; Xiao Han; Peiling Cai; Congcong Zhao; Anran Fu; Kun Liu; Xuli Tang; Guoqiang Li (Phytochemistry, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

ISFE-Net: An important spatial feature extraction network for UAV-Based hyperspectral water quality monitoring in rivers - Jiahao Chen; Yi Xiao; Zheng Wang; Xiran Li; Xuan Zhang; Fanghua Hao; Hongtao Duan; Yongshuo Fu (Journal of Hydrology, 2026)

Nitrogen deposition accelerates litter decomposition in peri-urban forests with species-specific responses - Zhuangzhuang Qian; Ranran Fu; Liu Liu; Chunhui Li; Qingshui Yu; Jinsheng Li; Ruoxian Fu; Xiao Tao (Journal of Environmental Management, 2026)

Hydrothermal Fe deposits and associated critical metals - Xiao-Wen Huang; Xin-Fu Zhao; Xiaochun Li (Journal of Asian Earth Sciences, 2026)

Subduction erosion intensifying carbonate-rich material recycling revealed by Mg-Zn isotopic evidence from high-Mg andesites in central Tibet - Jialiang Li; Wei-Qiang Ji; Xiao-Chi Liu; Jingao Liu; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

The role of geography and regional climate in shaping the chemical profiles and biological potentials of Citrus essential oils - Wenbin Xiao; Jiajing Guo; Yanfang Liao; Yanjiao Fu; Zixuan Li; Tongping Zhang; Ting Liu; Yangbo Xiao; Xuebo Shang; Zhipeng Gao; Yang Shan (Food Chemistry, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

High-resolution chronostratigraphic framework and spatiotemporal evolution of Carboniferous-Permian source rocks in the Junggar Basin and its periphery - Zhangshuai Hou; Xiangdong Wang; Dongming Zhi; Yong Tang; Qiong Wu; Hua Zhang; Jian Cao; Dongsheng Xiao; Guobin Fu; Menglin Zheng; Xuefeng Qi; Yaofeng Cai; et al. (Science China Earth Sciences, 2026)

The persistent threat of Niphades castanea to China’s chestnut across three major river basins - Bin Mao; Yue Fu; Ya-Bo Liu; Hui-Ling Yang; Yun-Li Xiao (New Forests, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

An Adaptive Optimization Method for Moored Buoy Site Selection Integrating Ontology Reasoning and Numerical Computation - Miaomiao Song; Haihui Song; Shixuan Liu; Xiao Fu; Bin Miao; Wenqing Li; Keke Zhang; Wei Hu; Xingkun Yan (Journal of Marine Science and Engineering, 2025)
With the growing diversity and complexity of marine monitoring requirements, the scientific deployment of moored buoys has attracted increasing attention. To address the limitations of traditional methods—such as inconsistent knowledge representation, insufficient logical reasoning capacity, and poor adaptability to dynamic marine environments—this study proposes an adaptive optimization method for moored buoy site selection integrating ontology reasoning and numerical computation. The proposed approach constructs an ontology model covering key concepts such as buoy specifications, monitoring objectives, and deployment requirements, and further defines formalized reasoning rules to enable automated judgment of deployment feasibility, sensor configuration, and spatial conflict resolution for moored buoy siting. Based on this semantic framework, a spatio-temporal comprehensive variation index (STCVI) is established by integrating temperature, salinity, and current velocity to characterize dynamic oceanographic conditions. Furthermore, a coverage-first greedy algorithm is designed to determine buoy deployment locations, enabling dynamic optimization and environmental adaptability of the buoy station layout. To verify the feasibility and adaptability of the proposed method, simulation experiments are conducted in the Beibu Gulf. Two layout scenarios—an appending layout with existing buoys and an independent layout without existing buoys—are designed to test the method’s adaptability under different deployment conditions. By combining Voronoi spatial partitioning and nearest-neighbor distance analysis, the optimized results are quantitatively evaluated in terms of spatial uniformity and observational effectiveness. The results indicate that the proposed method effectively enhances the spatial rationality and monitoring efficiency of buoy deployment, demonstrating strong generality and scalability.

Review of Sargassum thunbergii (Fucales, Phaeophyta): phycology, chemistry, bioactivity, and application - Xueyu Wang; Dandan Xiao; In-Kyu Yeo; Lei Wang; Yiqiao Li; Jia Fu; Yunhua Fu; Suengmok Cho; You-Jin Jeon; Fengqi Yang (Algae, 2025)
Sargassum thunbergii is a large brown seaweed endemic to the Northwest of Pacific Ocean, widely distributed in the warm temperate coastal waters of South Korea, China, and Japan. It is abundant in resources and has a long history of application, widely used in food, medicine, and feed. In recent years, it has also been used to restore marine ecology. To date, only one review has been published on Sargassum thunbergii aquaculture. Therefore, by investigating the international definitive data repository (ScienceDirect, PubMed, Web of Science, ACS Publications, Springer, etc.) and collecting 92 kinds of literature closely related to phycology, chemistry, biological activity, and applications, herewith a comprehensive and systematic summary and exposition, enveloping the classification and distribution, botanical characteristics, and physiological and biochemical differences of Sargassum thunbergii ; involving 7 chemical classifications of 117 derivatives substances embracing 12 new and 6 first-isolated excluding polysaccharides; mainly including 11 types of pharmacology in vivo and in vitro; evaluating the potential applications related on medicine, healthcare, aquaculture, and marine restoration. This review is expected to provide forward-looking scientific perspectives and act as a valuable reference for future studies, development, and utilization of Sargassum thunbergii .

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Integrating lewis acid/base pairs and hydroxyfunctional groups as dual adsorption sites into porous biochar fiber for enhanced iodine capture - Hongquan Fu; Xiao Wang; Liping Li; Zhenyang Li; Jinming Chang; Fang Liao; Hejun Gao; Juan Zhang; Yunwen Liao (Journal of Water Process Engineering, 2025)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Study on the effects of representative spice polyphenols on the in vitro digestive properties of tilapia myofibrillar protein and its mechanism of action: based on physical and chemical properties and enzyme activity - Zirui Fu; Jun Li; Ya Wei; Jianwei Cen; Huan Xiang; Xiao Hu; Chunsheng Li; Yanyan Wu; Shengjun Chen; Yongqiang Zhao; Hui Huang; Shuxian Hao (Food Chemistry, 2025)

Massive carbon storage in the upper mantle via diapirism of subducted continental sediments - Jialiang Li; Wei-Qiang Ji; Xiao-Chi Liu; Jingao Liu; Matthew J. Kohn; Fu-Yuan Wu (Earth-Science Reviews, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Injectable nanocomposite hydrogel with antibacterial/osteogenic dual functions for synergistic repair of infectious bone defects in hyperlipidemia microenvironment - Yongkai Wang; Yunhan Sun; Jiaming Song; Dongchen Fa; Yuting Qu; Jiayi Li; Xiao Fu; Li Ma (Chemical Engineering Journal, 2025)

Nonflammable localized high-concentration electrolytes with 1,3-dioxolane coordination regulation - Caiyun Wang; Ying Xiao; Guozhen Chen; Linming Bai; Tianji Fu; Xin Ma; Zhaoqing Jin; Xiaobin Hong; Juntao Zuo; Dezhan Li (Chemical Engineering Journal, 2025)

Synergistic Enhancement of Cobalt Adsorption by Graphitization and Magnetic Modification of Biochar: Synthesis, Characterization, Performance and Mechanism - Hui Liu; Chen Li; Zhichao Fan; Zhirui Dou; Beibei Lu; Xiao Fan; Xiaohui Ji; Jinlong Lai; Qian Fu; Songlin Gong; Xinna Wang; Jie Liu (Water, Air, & Soil Pollution, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Cryo-EM structures of mycobacteria MmpL5-AcpM complex - Delin Li; Xiaokang Zhang; Kai Yuan; Xiaomin Ma; Yucheng Wang; Pu Han; Junqing Sun; Tianling Guo; Xuefei Pang; Kefang Liu; Yan Wu; Yingxia Liu; et al. (Science China Life Sciences, 2025)

Screening of Lactic Acid Bacteria Strains from Chinese Fermented Food (Suanshui) and its Protective Effect on Acute Liver Injury in Mice - Fei Wang; Xiang Li; Qi Wang; Qian Jin; Shujie Xu; Li Tang; Zihan Zeng; Aikun Fu; Jinhui Zhu; Qiao Zhang; Rongchang Yang; Yingping Xiao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Impaired endothelial cell-derived CX3CL1-mediated macrophage efferocytosis in hypertrophic cardiomyopathy based on multi-omics analysis - Yan Zhang; Xin Yan; Xiao-lei Fu; Hai-bing Yang; Yi-min Yan; He-fan He; Li Yang (Inflammation Research, 2025)

Glycemic status-dependent proteomic signatures of biological aging for health risk prediction - Jiang Li; Jie Li; Xiaoqin Xu; Yuefeng Yu; Wenqi Shen; Ying Sun; Yanqi Fu; Xiao Tan; Ningjian Wang; Yingli Lu; Bin Wang (GeroScience, 2025)

Comprehensive Geophysical Characteristics and Exploration Significance of the Xiarihamu Super-Large Copper-Nickel Deposit in the East Kunlun Metallogenic Belt - Ji-en Dong; Bao-chun Li; Tao Wang; Yu-long Li; Xiao-jun Dong; Fu-chun Wang; Hai-kui Tong; Zhen-hua Zheng; Hua Li; Peng Wang (Applied Geophysics, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Unlocking the potential of fruit and vegetable waste: Sustainable biomanufacturing strategies for synergistic nutrient recovery and high-value bioproduct synthesis - Ziyi Fan; Zhipeng Gao; Yanjiao Fu; Yanfang Liao; Wenbin Xiao; Yunlong Ding; Chenqi Yang; Xin Li; Gaoyang Li; Donglin Su; Yang Shan; Jiajing Guo (Trends in Food Science & Technology, 2025)

An innovative boundary surface model integrating strain rate effect and its application in assessing sliding resistance of a movable subsea mudmat - Zhong Xiao; Zongquan Li; Pan Hu; Xiang Wang; Dengfeng Fu; Zhifa Yu; Xu Liu (Soil Dynamics and Earthquake Engineering, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

An innovative theoretical model for optimizing ball diameter in tumbling mills - Yunxiao Li; Qingfei Xiao; Yanxiong Fu; Saizhen Jin; Guobin Wang; Mengtao Wang; Boyuan Sun; Houyuan Tian; Xiaobo Liu; Jiahao Tian (Minerals Engineering, 2025)

The protein kinase MLOP1 mediates pectin fragment signaling and feedback regulation of cell wall synthesis - Xiaohui Liu; Jingjing Sha; Qingyao Li; Shuai Yuan; Jialin Tao; Shihan Fu; Pu Gan; Qiuyan Lan; Johannes Liesche; Chaowen Xiao (Journal of Plant Physiology, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Stratum corneum triboelectric nanogenerator - Weihao Zhai; Wei Li; Chongyang Fu; Yidan Xiao; Qizheng Li; Xiaoxiong Wang; Lei Chen (Chemical Engineering Journal, 2025)

Reactive oxygen species activatable nanotherapeutics for evaluating and relieving nanoplastics-induced oxidative stress - Lili Fu; Yan Huang; Xiao Sun; Xinlei Wang; Shuang Li; Xiaoyan Wang; Qi Kang; Dazhong Shen; Lingxin Chen (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Cu nanowire arrays on electroless deposited cu foam for efficient electrocatalytic formaldehyde selective conversion to co-produce H2 and valuable chemicals - Chunyi Ye; Yang Yang; Shujing Chen; Chunhua Liu; Xiao-Qing Sun; Danni Liu; Jiujun Zhang; Jing-Li Luo; Xian-Zhu Fu (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Study on Performance Optimization and Failure Law of Fly Ash-Coal Gangue Backfill - Fu-zhou Qi; Zhen Li; Song Yin; Ju-dong Li; Xiao-yu Liu; Kai Wang; Wei-jian Liu; Shui-sheng Yu; Zhi-liu Wang (Applied Geophysics, 2025)

Bivalent vaccination with Edwardsiella tarda and Aeromonas salmonicida protected freshwater fish after challenge and consists a strategic approach against pathogens - Simei He; Guofan Zhang; Yuyuan Peng; Kunyan Li; Jiajie Xie; Ke Zhang; Wen Fu; Yamei Xiao; Liqiu Xia; Shengbiao Hu (Aquaculture, 2025)

Experimental study of rock-machine interaction responses in sandstone with distributed boreholes through TBM tunnelling test - Wei-Qiang Xie; Xiao-Li Liu; Xiao-Xiong Zhou; Nai-Fu Deng (Tunnelling and Underground Space Technology, 2025)

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

A novel approach for tracking the diurnal dynamics of chlorophyll-a in lakes using UAV hyperspectral images - Yi Xiao; Xiran Li; Jiahao Chen; Shihui Guo; Yue Xu; Xingyu Nie; Yangjing Nie; Fanghua Hao; Yongshuo Fu (Journal of Hydrology, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Intrinsic electron transfer kinetics of electroactive granular sludge bioanode boosting bio-electro-Fenton efficiency - Bao-Gang Fu; Shu-Na Li; Xiangtong Zhou; Xiang Xiao; Liang Cheng; Yang-Yang Yu (Journal of Environmental Chemical Engineering, 2025)

Synergistic highly sensitive electrochemical detection of enrofloxacin using Eichhornia crassipes-derived carbon dots and molecularly imprinted polymer networks - Chang-Hong Wang; Yi-Yue Tang; Yan-Jun Li; Fu-Lan Xiao; Lian-Di Zhou; Qi-Hui Zhang; Chun-Su Yuan (Journal of Environmental Chemical Engineering, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Mitochondrial DNA leakage and micronucleus formation activate the cGAS–STING pathway in aristolochic acid I-induced nephritis - Yu yang Lei; Yu shi Hu; Yi yi Cao; Jing Xi; Yu ning Ma; Xiao hong Zhang; Qin wen Gao; Ji an Fu; Xin yu Zhang; Li Su; Yang Luan (Food and Chemical Toxicology, 2025)

Superwetting aqueous electrolyte for highly stable zinc anodes - Yurou Wu; Huijian Wang; Meilan Xie; Kai Fu; Zhendong Li; Xingyuan Dai; Jiarui Zhang; Lihan Wang; Xiaoshu He; Yidan Luo; Sheng Ouyang; Wen He; et al. (Chemical Engineering Journal, 2025)

Polyacrylic acid promotes anti-passivation and electron-donation of boronized nanoscale zero-valent iron during groundwater remediation - Zelong Zheng; Lihang Ma; Xiaobin Liao; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Experimental study of geogrid role on long-term settlement in geosynthetic-reinforced pile-supported embankment subjected to cyclic loading - Kai-Fu LIU; Shi-Yu XU; Wei-Qiang FENG; Kai-Ren XUE; Yu-Xiao Li (Transportation Geotechnics, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Mechanisms of microbial inhibition of freeze-thaw hydraulic alternating erosion in cold black soil region: Reconstructing soil structure with indigenous bacteria - Tianxiao Li; Zhaoxing Xiao; Qiang Fu; Fanxiang Meng; Renjie Hou; Shunli Zheng; Mo Li; Dong Liu; Fanying Kong (Journal of Environmental Management, 2025)

Phase engineering of PtCo alloy supported on N-doped carbon via pyrolysis of ZIF and carbon black for efficient and durable oxygen reduction reaction - Dongju Fu; Zhao Hu; Jinghui Xun; Xiao Yu; LuYang Wang; Shaozhong Zeng; Fengjiao Li (Fuel, 2025)

Corrigendum to “Modulating the density of Co3N/CFs active site by optimizing the micro-structure for overall water splitting electrocatalysis” [Chem. Eng. J. 515 (2025) 163505] - Qiusen Liu; Tingzheng Fu; Hongbiao Xiao; Ye Yu; Zhiqing Che; Yixing Zhang; Anran Chen; Mian Li; Tingting Liu (Chemical Engineering Journal, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Sequence of middle-lower Ordovician in Shunbei area of Tarim Basin, China, and its geological significance - Rui Xiong; Heng Fu; Yong Li; Caizhu Xie; Ronggang Wang; Shaoze Zhao; Chuan Xu; Chongyang Xiao (Carbonates and Evaporites, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Effects of high temperature on gonadal development of gynogenetic Megalobrama amblycephala and acquisition of fertile pseudo-male fish - Wen Fu; Ze Li; Xin Ren; Feng Liu; Wenbin Liu; Jinhui Liu; Liangyue Peng; Yamei Xiao (Aquaculture, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

The RING-finger ubiquitin E3 ligase RFEL1 targets wheat NPR3 for degradation to confer broad-spectrum resistance against biotrophic fungal pathogens - Liuhui Qiao; Kunpu Zhang; Jinyan Li; Ziming Zhang; Xiao Sun; Huiyun Liu; Ziyue Li; Nannan Ni; Ximei Ma; Jianhui Zhao; Guangwei Li; Xiaohuan Jin; et al. (Molecular Plant, 2025)

Decoding the role of Bacillus: Unraveling the transformation of bioactive compounds during the aging of Pericarpium Citri Reticulatae - Yanjiao Fu; Chao Wang; Zhipeng Gao; Yanfang Liao; Zixuan Li; Wenbin Xiao; Mingwang He; Yuwen Wang; Fuhua Fu; Gaoyang Li; Donglin Su; Lvhong Huang; et al. (Food Research International, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

Diazotrophic community difference between specialists and generalists in response to arsenic and antimony contaminations - Yan Wang; Yiqun Xiong; Yongbin Li; Liu He; Mingyue Chen; Rongbin Fu; Yu Xiao (Environmental Research, 2025)

Nitrogen deposition reshapes biological nitrogen fixation and soil diazotrophic communities across urban and rural forests - Ruoxian Fu; Dianlong Ge; Jinsheng Li; Yuanchun Yu; Zhuangzhuang Qian; Xiaoniu Xu; Chunhui Li; Biao Zhu; Xiao Tao (CATENA, 2025)

The combination of linkage mapping, genome-wide association study, and dynamic transcriptome analysis reveals conserved candidate genes for salt tolerance in maize - Ziyi Xiao; Zhenyuan Pan; Xinxin Liu; Xueqing Zheng; Guantao Wang; Yayu Fu; Mengmeng Li; Bin Hou; Xuhua Li; Ming Zhang; Chunlan Jia; Fazhan Qiu (Theoretical and Applied Genetics, 2025)

Multi-omics study reveals a light-dependent regulatory network of flavonoid biosynthesis in lettuce (Lactuca sativa L.) - Yuting Xiang; Shuxin Zheng; Hsihua Wang; Bang Chen; Rao Fu; Tao Huang; Li Zhang; Bo Song; Yuejian Li; Qichang Yang; Xiao Yang; Yang Zhang (Science China Life Sciences, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Karyotype and evolution trend analysis of seven diploid accessions and their autotetraploid lines of Tartary buckwheat native to China - Li-kun Lian; Pei Zhang; Xiao-fen Wu; Yi-zhong Zhang; Qing-fu Chen (Genetic Resources and Crop Evolution, 2025)

Mechanisms of endothelial senescence and vascular aging - Qiao Li; Zonghao Qian; Yuzhen Huang; Xiao Yang; Jiankun Yang; Nanyin Xiao; Guangyu Liang; Heng Zhang; Yanguang Fu; Yan Lin; Cuntai Zhang; Anding Liu (Biogerontology, 2025)

Analysis of the response mechanism in lipid degradation of key gene LDH1 knockout strains of Saccharomyces cerevisiae under levulinic acid stress - Yulei Chen; Jiaye Tang; Qian Li; Wenli Xin; Ximeng Xiao; Borui Mou; Jialian Li; Fujia Lu; Chun Fu; Wencong Long; Hong Liao; Xuebing Han; et al. (Archives of Microbiology, 2025)

Inhibitory effects of flavonoids and alkaloids from the traditional antihyperglycemic herb Polygonatum kingianum var. grandifolium on α-glucosidase activity - Qing-Dong Ma; Xu-Juan Fu; Xiao-Qin Xiong; Dong-Mei Liu; Zhuo-Jun Li; Wei Gong; Dong-Qin Guo; Dong-Yang Yi (Natural Product Research, 2025)

Theoretical and numerical study of the failure mechanism and minimum safety thickness of water-resistant rock mass in layered karst tunnels - Qianfeng Xiao; Yang Wang; Yajing Li; Leilei Jin; Wenxi Fu; Fei Ye (Tunnelling and Underground Space Technology, 2025)

Ore-forming fluid for the formation of banded iron formation-hosted high-grade magnetite ores of the North China Craton: Constraints from pyrite trace elements and sulfur isotopes - Yi Wang; Li-Xing Li; Hou-Min Li; Jian-Fei Fu; Yang Dai; Xiao-Hui Wang; Xuan Wu (Journal of Asian Earth Sciences, 2025)

MOF derived bimetallic-nanoreactor as peroxymonosulfate activator for highly efficient levofloxacin degradation: Performance and mechanism - Xiangyu Li; Xinxi Fu; Jingdong Wu; Xiao Fu; Jiahao Huang; Yonghua Chen (Chemical Engineering Journal, 2025)

Modulating the density of Co3N/CFs active site by optimizing the micro-structure for overall water splitting electrocatalysis - Qiusen Liu; Tingzheng Fu; Hongbiao Xiao; Ye Yu; Zhiqing Che; Yixing Zhang; Anran Chen; Mian Li; Tingting Liu (Chemical Engineering Journal, 2025)

Trace cobalt accelerates the structural reconstruction to generate high-valence nickel for water-splitting in seawater media - Huilin Zhao; Silu Liu; Fengyuan Tian; Hongdong Li; Liantao Xin; Weiping Xiao; Guangrui Xu; Dehong Chen; Tianyi Ma; Elmurod Egamberdiev; Sardor Donaev; Yingxia Zong; et al. (Chemical Engineering Journal, 2025)

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

Physical model tests on the lateral cyclic behaviour of monopile in marine clay - Kai-Fu Liu; Yu-Xiao Li; Wei-Qiang Feng; Yue-Dong Xu; Zhi-Qing Zhang (Ocean Engineering, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Advanced oxidation processes for the degradation of tralomethrin: Impacts on zebrafish embryonic development - Yueping Huang; Rongkai Bao; Shanshan Guo; Peng Xiao; Huihui Fu; Wenhua Li (Journal of Environmental Management, 2025)

A novel Ce-Bi2MoO6/CeVO4 Z-scheme heterojunction for peroxymonosulfate activation toward levofloxacin photodegradation - Xin Nie; Jun Li; Guohua Dong; Yong Li; Xinjia Zhang; Wenzhi Zhang; Qiu Fu; Tianyuan Xiao; Liming Bai (Journal of Environmental Chemical Engineering, 2025)

The effect of catalyst preparation methods on biomass hydrothermal liquefaction: Exploring cleaner and more efficient pathways for catalytic hydrothermal liquefaction of biomass - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Si-hao Ling; Fu-xiang Yang; Shun-guo Wang (Fuel, 2025)

Facile and green synthesis of nanocarriers from chondroitin sulfate-based and whey protein isolate with improved stability and biocompatibility for anthocyanins protection - Zixuan Li; Zhipeng Gao; Donglin Su; Zhipeng Su; Yanjiao Fu; Wenbin Xiao; Fuhua Fu; Gaoyang Li; Lvhong Huang; Jiajing Guo; Yang Shan (Food Chemistry, 2025)

The association between greenspace exposure and sperm quality: A retrospective cohort study focusing on sperm kinematics and the influence of buffer settings - Sixuan Zeng; Tingting Yang; Run Tian; Xin Jin; Lu Zhang; Fuping Li; Leyao Fu; Jiarui Cai; Junhao Liao; Guishuang Song; Xiaoli Luo; Yujue Wang; et al. (Environmental Research, 2025)

Correction: Stability Evaluation of Lyotropic Liquid Crystalline Precursor for the Co-delivery of Chlorhexidine and Silver Nanoparticles - Fangqin Fu; Xin Li; Tengyi Zheng; Xiao Xia; Minqun Du; Zhengwei Huang; Ying Huang; Xin Pan; Chuanbin Wu (AAPS PharmSciTech, 2025)

An Ecosystem-Based Approach to Evaluating Impacts of Fisheries Management on Ecosystem Restoration in a Chinese Subtropical Yangming Reservoir - Haibo Gong; Chengjie Yin; Jinxiang Yu; Jun Xiao; Zhijie Yu; Xuejun Fu; Bin Huang; Xiya Wu; Caigang Li (Fishes, 2025)
This study delves into the ecological implications of diverse fishery patterns on aquatic ecosystems, centering on environmental parameters, species richness, and nutrient dynamics. Using the ecological fishery management model of Yangming Lake as a case, it evaluates its influence on water quality improvement, species diversity promotion, and ecosystem stability maintenance. From 2018 to 2022, the Shannon–Wiener index in Yangming Lake increased by 17.34%, and water quality significantly improved, with phytoplankton biomass decreasing by 95.5%, total nitrogen content dropping by 33.69%, and permanganate index declining by 30.75%. Although ecological fisheries demonstrate certain effectiveness in tackling invasive species, further in-depth research is needed. This study emphasizes the importance of striking a balance between fishery development and ecological protection, in line with the United Nations Food and Agriculture Organization’s “blue transformation” strategy. Our findings offer valuable insights for sustainable fisheries development and highlight the necessity of customized management strategies to protect biodiversity and ecosystem resilience. Future research will focus on exploring the long-term ecological effects of ecological fisheries and the role of native carnivorous fish in controlling invasive species.

Transcriptome analysis of gills reveal the key metabolism-related genes and pathways response to ammonia nitrogen stress in Scylla paramamosain - Chaoyue Wang; Xiao Liu; Jie Zhou; Sixiang Wang; Xia Zheng; Zehao Li; Yuanyuan Fu; Zhongwen Jin; Lei Liu (Frontiers in Marine Science, 2025)
Ammonia nitrogen is highly toxic to crustaceans; however, studies investigating the molecular mechanisms underlying its metabolism and excretion in these organisms remain scarce. The present study aims to identify key genes and investigate the molecular mechanisms in response to ammonia nitrogen using RNA sequencing in Scylla paramamosain , a key economic crab species in Asia that is subjected to ammonia nitrogen stress in aquaculture. The median lethal concentrations (LC50) of ammonia nitrogen exposure were determined as 325.4 mg/L for 24 hours, 253.7 mg/L for 48 hours, and 198.2 mg/L for 72 hours. Subsequently, crabs were exposed to 325.13 mg/L NH4Cl for durations of 24, 48, and 96 hours, followed by transcriptome sequencing to identify differentially expressed genes (DEGs) related to ammonia nitrogen metabolism in the anterior and posterior gills of Scylla paramamosain . Ammonia nitrogen stress caused significant damage to the morphology and structure of the gills, with prolonged exposure leading to further damage, including cellular vacuolization and narrowing of the gill hemolymph chambers. A total of 184.66 Gb of clean data and 36,439 DEGs were obtained, including 7,880 DEGs in the anterior gill and 28,559 DEGs in the posterior gill, which were implicated in the regulation of ammonia nitrogen metabolism-related pathways. KEGG enrichment analysis revealed that ammonia nitrogen stress induced changes in the expression of metabolism- and immune-related genes. Following ammonia nitrogen stress, the expression of ammonia nitrogen metabolism-related genes (punA, XDH, rocF, allB) in the anterior gill was upregulated, whereas the expression of genes in the posterior gill (GART, rocF, alc) was downregulated. These results indicate that ammonia nitrogen stress enhances ammonia nitrogen metabolism in the anterior gill, while inhibiting this process in the posterior gill. The expression of immune-related genes (Hsp10, Hsp70, Hsp90, CTL) in both the anterior and posterior gills was downregulated following ammonia nitrogen stress, suggesting that ammonia nitrogen stress diminished the organism’s immune capacity. These findings provide a theoretical foundation for understanding the molecular mechanisms regulating ammonia nitrogen metabolism and for improving the artificial culture of Scylla paramamosain .

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Synergistic effects of bio-organic fertilizer and different soil amendments on salt reduction, soil fertility, and yield enhancement in salt-affected coastal soils - Meng Xiao; Shengguo Jiang; Jinbiao Li; Wenping Li; Pengxiao Fu; Guangming Liu; Jinlin Chen (Soil and Tillage Research, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Respiratory rate detection of dairy cows based on infrared thermography in head movement scenarios - Xinchao Chen; Baisheng Dai; Xinjie Wang; Yanxing Li; Xiao Fu; Xin Dai; Hangshu Xin; Yang Li; Weizheng Shen (Journal of Thermal Biology, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Long-term study of Citrus changshan-huyou Y.B. Chang essential oil: Chemical transformations and their impact on antibacterial efficacy - Wenbin Xiao; Jiajing Guo; Yanjiao Fu; Zixuan Li; Tongping Zhang; Mingwang He; Ting Liu; Yangbo Xiao; Xuebo Shang; Fuhua Fu; Gaoyang Li; Donglin Su; et al. (Food Chemistry, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

Trace Pt Induced electron-enriched Ru to boost interfacial water-activation for alkaline hydrogen generation under industrial condition - Qihao Wang; Yusen Chen; Xingchao Zang; Hongdong Li; Weiping Xiao; Yingxia Zong; Guangying Fu; Jinsong Wang; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2025)

Impact of occupancy density and source location on inhalational exposure of infectious respiratory particles in a naturally ventilated fever clinic - Shuo Liu; Ying Wang; Yanling Xiao; Weiqi Guo; Yifan Li; Yiran Lu; Yalin Liu; Yi Wang; Linzhi Fu; Bilong Feng; Li Liu (Building and Environment, 2025)

Mechanisms of urea combined with nitrification inhibitors on prompting cadmium uptake and accumulation in rape (Brassica napus L.) - Li Li; Lin Chen; Xin Fu; Zhong Hu; Qingru Zeng; Xiao Deng; Yang Yang; Si Luo (Plant and Soil, 2025)

Avian influenza A(H5N6) virus detected during live-poultry market surveillance linked to a human infection in Changsha, China, from 2020 to 2023 - Zheng Huang; Rusheng Zhang; Dong Yao; Huiyuan Fu; Lingzhi Li; Shan Xiao; Xinhua Ou; Mingzhong Xu; Qing-Bin Lu; Xuewen Yang (Archives of Virology, 2025)

Intelligent quality control method for marine buoy data based on transformer encoder and BiLSTM - Miaomiao Song; Saiyu Gao; Shixuan Liu; Yuzhe Xu; Shizhe Chen; Jiming Zhang; Wenqing Li; Keke Zhang; Xiao Fu (Frontiers in Marine Science, 2025)
Ocean moored buoys are essential ocean monitoring devices that are permanently moored in the sea to collect real-time hydrological and meteorological data. In response to the anomalies and missing data in datasets collected from ocean moored buoys, this paper innovatively established an intelligent quality control Transformer-Encoder-BiLSTM model. This model can impute missing data and identify anomalies in buoy datasets. The model first uses the multi-head attention mechanism of the Transformer Encoder to extract global features from time-series data of buoy observations. Subsequently, it utilizes the BiLSTM network for temporal reasoning training to capture dynamic changes within the time series, predicted data. Finally, using the predicted data as a benchmark, the model conducts anomaly detection, fills in missing values, and rectifies stuck values. We conducted a series of comprehensive experiments, with the data from Buoy No. 0199 in Qingdao, China as an illustrative example. The experimental results indicate that the performance indicator R² of the model is above 0.9, the accuracy of quality control is above 97%, while both precision and recall are above 84%. The F1 scores range between 81.61% and 90.09%. These experiments demonstrate that this method exhibits high accuracy and efficiency in filling in missing data, rectifying stuck values and identifying anomalous data, showing broad application potential.

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Highly efficient and convenient QuEChERS using ZIF-67 derived magnetic nanoporous carbon for determination of carbamate pesticides in various vegetable and fruit samples - Zi-Ling Li; Xiao-Run Qi; Yi-Heng Xu; Jia-Qi Zhao; Gui-Fu Zuo; Man-Man Wang (Food Chemistry, 2025)

Fucoxanthin promotes the conversion efficiency of alpha-linolenic acid in feeding to docosahexaenoic acid in quail egg yolk - Wen-Lei Guo; Shuai-Shuai Fu; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Yu-Ming Wang; Tian-Tian Zhang (Food Chemistry, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Chemical constituents of Xylanche himalaica and their chemotaxonomic significance - Wei Nie; Li-Ping Feng; Jin-Fu Wan; Xiao-Hui Li; Ying-Jie Zhang; De-Huan Fu; Qian Li (Biochemical Systematics and Ecology, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Regulatory Roles of Exosomes in Aging and Aging-Related Diseases - Nanyin Xiao; Qiao Li; Guangyu Liang; Zonghao Qian; Yan Lin; Heng Zhang; Yangguang Fu; Xiao Yang; Cun-Tai Zhang; Jiankun Yang; Anding Liu (Biogerontology, 2025)

Responses of zebrafish to chronic environmental stressors: anxiety-like behavior and its persistence - Xiao-hong Li; Cheng Fu; Xue-ting Tan; Shi-jian Fu (Frontiers in Marine Science, 2025)
Introduction Fish in natural ecosystems face long-term environmental stressors, with anxiety being a critical stress response. This study investigates how chronic stressors—predators, social isolation, and caffeine—affect anxiety-like behavior and cortisol levels in zebrafish ( Danio rerio ), and examines the persistence of these effects post-stressor removal. Methods Zebrafish were exposed to three stressors for 14 days. Anxiety-like behavior and cortisol levels were measured for up to 28 days following the removal of the stressors. Results Chronic predator stress significantly increased anxiety-like behavior and cortisol levels, persisting for at least seven days post-removal. Social isolation reduced anxiety-like behavior and cortisol levels, with effects lasting no less than one day after re-socialization. Caffeine induced temporary anxiolytic effects, reversing one day post-withdrawal and persisting for at least seven days, while cortisol levels remained elevated. Discussion Zebrafish exhibit stressor-specific behavioral and physiological changes with varying persistence. These findings enhance understanding of fish responses to environmental stressors, offering insights into their survival strategies and ecosystem health.

Multi-scale spatiotemporal patterns of urban climate effects and their driving factors across China - Panli Cai; Runkui Li; Jingxian Guo; Zhen Xiao; Haiyu Fu; Tongze Guo; Tianyi Wang; Xiaoping Zhang; Qun Xu; Xianfeng Song (Urban Climate, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Preparation of diacylglycerol by lipase-catalyzed glycerolysis in the presence of polar adsorption materials - Xiao Tang; Houyue Li; Jialing Gu; Yijie Fu; Junwen Yu; Zongrun Li; Yuqi Li; Xiaowen Wang; Xiaosan Wang (Food Chemistry, 2025)

Frabrication of carboxymethylchitin nanofibers and fish gelatin hybrid gels with robust gel performance - Rongqiang Chen; Shuai Zhang; Jiao Jiao Sun; Lijuan Xu; Yuan Duan; Fengchen Li; Yanhui Han; Xiao Fu; Meng Wang; Yong Hong Meng; Yurong Guo (Food Hydrocolloids, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Room-temperature CO2-to-carbon conversion facilitated by copper-gallium liquid metal - Xiao Chen; Jiacheng Liu; Qing Wang; Mengmeng Fu; Yunlong Li; Jialun He; Wenjun Zhan; Litian Liu; Danfeng Jiang; Yingguo Li; Chao Yu (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Erwinia aeris sp. nov., A Novel Bacterium Isolated from the Surface of an Ore in Hubei Province, China - He-Bao Guo; Hong-Tu Zhu; Yi-Fan Zhang; Fu Yang; Xiao-Tong Ma; Shi-Gui Li; Hai-Lei Wei; Xiao-Xia Zhang (Current Microbiology, 2025)

Cxcl9 modulates aging associated microvascular metabolic and angiogenic dysfunctions in subcutaneous adipose tissue - Xin Fu; Yu Zhao; Xiwei Cui; Siyuan Huang; Yanze Lv; Chen Li; Fuxing Gong; Zhigang Yang; Xiaonan Yang; Ran Xiao (Angiogenesis, 2025)

Mulberry leaf extract reduces damage by regulating the oxidative response, immune response and intestinal flora of largemouth bass (Micropterus salmoides) under chronic heat stress - Bing Fu; Donglai Zhou; Xiaotong Qiu; Jieqiu Zheng; Qiong Yang; Yang Xiao; Sentai Liao; Qingrong Li; Dongxu Xing (Frontiers in Marine Science, 2025)
Chronic heat stress (HS) induces oxidative damage, low immunity, and intestinal flora disturbance of fish, posing great challenges to the aquaculture industry. As an important plant extract, mulberry leaf extract (MLE) has been shown to have antioxidant and immune-boosting properties. This study evaluated the protective effect of dietary MLE on HS-induced liver injury and intestinal flora disturbance in Largemouth bass ( Micropterus salmoides ) based on oxidative damage parameters, immune parameters, and intestinal flora composition. Fish were randomly assigned into three groups: CON group (ambient temperature, 26°C, basal diet), HS group (33°C, basal diet), and HS + MLE group (33°C, basal diet supplemented with 9 g/kg MLE). HS significantly decreased the final body weight, specific growth rate, intestinal villus length, muscular layer thickness, ACE and Chao1 indices, and lipase, trypsin, total superoxide dismutase (T-SOD), glutathione peroxidase (GPx), alkaline phosphatase (AKP), and lysozyme (LZM) activities, but significantly increased the feed conversion rate, aspartate aminotransferase (AST) activity, reactive oxygen species (ROS), malondialdehyde (MDA), complement 3 (C3) contents, and the relative abundances of Proteobacteria and Plesiomonas . Compared with the HS group, dietary MLE significantly improved lipase, trypsin, GPx, ACP, and LZM activities, and ACE and Chao1 indices in intestine, but significantly decreased the numbers of vacuoles and inflammatory cells, AST activity, and the GLU, MDA, and ROS contents. Dietary MLE also significantly up-regulated the mRNA expressions of gpx , tg f-β , il-10 , jnk2 , and bcl-2 , but down-regulated the mRNA expressions of il-8 , tnf-α , caspase-3 , atf4 , chop , ire1, traf2 , jnk1 , TRPV , MCU , and VDAC in liver. In conclusion, dietary supplementation with 9 g/kg MLE could improve the growth, immunity, and diversity of intestinal flora in heat-stressed largemouth bass, and alleviate hepatic injuries by regulating inflammation, oxidative stress, and apoptosis, providing a theoretical basis for the development of MLE as a treatment against HS.

Selective oxidation of nitrogenous heterocyclic compounds by heat/peroxymonosulfate in phenol-rich wastewater - Liangjie Wang; Zhengyi Sun; Jinrui Shi; Han Li; Tao Fu; Yi Xu; Ke Xiao; Huazhang Zhao (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

Mechanistic impact of Gracilaria bailinae extracts on photosynthesis and metabolism in Phaeodactylum tricornutum - Li-Gong Zou; Fu-Fang Wen; Xiao Zhang; Gang Li; Qing Wang; Hong-Ye Li; Yu-Feng Yang (Marine Environmental Research, 2025)

Using the Forel-Ule index (FUI) to track the water quality of subsidence water bodies across the life cycle of coal mining in eastern China - Wenqi Chen; Lijuan Chen; Yongping Wei; Linlin Ruan; Yanhua Fu; Wei Li; Tingting He; Wu Xiao (Journal of Environmental Management, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

SENP2 negatively regulates RIG-I/MDA5 mediated innate immunity in black carp - Yixia Chen; Jun Li; Jiaxin Fu; Lili Xiao; Jixiang Chu; Wei Qin; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2025)

Dual Hydrogen-Producing Formaldehyde-Water fuel cell for pollutant treatment and valuable chemical Co-generation - Yang Yang; Jianwen Liu; Munir Ahmad; Xiao-Qing Sun; Chunhua Liu; Shujing Chen; Jiujun Zhang; Jing-Li Luo; Xian-Zhu Fu (Chemical Engineering Journal, 2025)

All-solid-state wire-shaped micro-supercapacitors: A microfluidic approach to core-shell structured bacterial cellulose-GN/PPy fibers - Yue Jiao; Yao Wang; Huining Xiao; Jian Li; Changtong Mei; Qiliang Fu; Jingquan Han (Carbohydrate Polymers, 2025)

The Inversion of Seepage Parameters by Tidal and Barometric Response Methods: A Case Study of Shizhu Well with the Thick Aquifer Mixed with Mudstones - Qiuye Yang; Yan Zhang; Junliu Suwen; Xiao-long Sun; Tianming Huang; Junhua Hu; Shengwen Qi; Li-Yun Fu (Pure and Applied Geophysics, 2025)

Prenatal Exposure to Neonicotinoids and the Associations with Neonatal Birth Outcomes and Maternal Health in South China - Jinfeng Fu; Yao Yao; Zhihong Huang; Jiayin Huang; Jiayi Xu; Xiangyu Li; Junye Bian; Zhihui Guo; Qinru Xiao; Shaoyou Lu (Exposure and Health, 2025)

Shear strain prediction of reservoir landslide based on FBG monitoring and bagging-MLP algorithm - Jia Wang; Hong–hu Zhu; Xiao Ye; Feng Tian; Wei Zhang; Hou–zhi Li; Hua–fu Pei (Bulletin of Engineering Geology and the Environment, 2025)

Source characteristics and quantitative estimates of organic carbon composition in the intertidal zones of Jiaozhou Bay, China - Ke Liu; Jie Fu; Li Li; Daolai Zhang; Xiaotong Xiao (Marine Pollution Bulletin, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

A potential role for the interaction of Wolbachia surface proteins with the Drosophila microtubulin in maintenance of endosymbiosis and affecting spermiogenesis - Bin Mao; Ying-Ying Wang; Si-Ying Li; Yue Fu; Yun-Li Xiao; Yu-Feng Wang (Journal of Insect Physiology, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Enrichment of EPA and DHA in glycerides by selective enzymatic ethanolysis - Junwen Yu; Yijie Fu; Xiao Tang; Weijia Bao; Zongrun Li; Xiaowen Wang; Xiaosan Wang (Food Chemistry, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

Clinical efficacy and safety of vortioxetine as an adjuvant drug for patients with bipolar depression - Chunxiao Dai; Yaoyang Fu; Xuanwei Li; Meihua Lin; Yinbo Li; Xiao Li; Keke Huang; Chengcheng Zhou; Jian Xie; Qingwei Zhao; Shaohua Hu (Journal of Zhejiang University-SCIENCE B, 2025)

Inhibition of CB1R in the Hypothalamic Paraventricular Nucleus Ameliorates Hypertension Through Wnt/β-Catenin/RAS Pathway - Hong-Li Gao; Yu Yang; Hua Tian; Li-Yan Fu; Kai-Li Liu; Xiu-Yue Jia; Xiao-Lian Shi; Yu-Ming Kang; Xiao-Jing Yu (Cardiovascular Toxicology, 2025)

Multi-step gene set analysis identified HTR3 family genes involving childhood acute lymphoblastic leukemia susceptibility - Xiao Liu; Honghao Guo; Meiyun Kang; Wenfeng Fu; Huiqin Li; Hongsheng Ji; Jiou Zhao; Yongjun Fang; Mulong Du; Yao Xue (Archives of Toxicology, 2025)

A two-stage coordinated restoration scheme of hybrid AC/DC distribution grid considering cold load pickup and resilience enhancement - Hang Yu; Fu Xiao; Hanbei Zhang; Wei Liao; Yanxue Li (Sustainable Cities and Society, 2024)

A novel quantitative detection method for soil organic matter content based on visible to near-infrared spectroscopy - Jie Huang; Zhizhong Mao; Dong Xiao; Yanhua Fu; Zhenni Li (Soil and Tillage Research, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Introduction to special issue LED 2023 - Naomi Porat; Frank Preusser; Bo Li; Christophe Falgueres; Fu Xiao; Georgina King; Jakob Wallinga; Julie Durcan (Quaternary Geochronology, 2024)

Polygonati Rhizoma varieties and origins traceability based on multivariate data fusion combined with an artificial intelligence classification algorithm - Peng Chen; Chenghao Fei; Rao Fu; Xiaoyan Xiao; Yuwen Qin; Xiaoman Li; Zhijun Guo; Jianmin Huang; De Ji; Lin Li; Tulin Lu; Qiaosheng Guo; et al. (Food Chemistry, 2024)

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Environmental exposure to cadmium induces olfactory neurotoxicity in fire ants and the molecular basis - Xiaohui Xiao; Wenzhen Zhao; Yikang Shao; Changyuan Hu; Jinlong Liu; Guoqing Zhang; Fuxiang Yang; Jing Zhao; Yueguan Fu; Lei Li; Man-Qun Wang; Aiming Zhou (Environmental Pollution, 2024)

Ru-M (Fe, Co, Ni) onto Nitrogen-doped Two-dimensional Carbon Nanosheets through Microwave Approach with Strong Metal-support Interactions for overall Water-splitting - Huizhen Wang; Xueying Luan; Hongdong Li; Yingxia Zong; Weiping Xiao; Guangrui Xu; Dehong Chen; Guangying Fu; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

The core phoD-harboring bacteria promote wheat phosphorus uptake by enhancing alkaline phosphatase activity under long-term fertilization - Shuobing He; Yuying Ma; Teng Yang; Xiao Fu; Li Nie; Jiasui Li; Daozhong Wang; Yanhua Su; Haiyan Chu (Soil Ecology Letters, 2024)

Development and application of a refined subchannel analysis code for lead-based wire-wrapped bundles - Yubo Sun; Yao Xiao; Junlong Li; Junsen Fu; Maolong Liu; Hui Guo; Xiaoyan Tian; Xinbiao Jiang; Lixin Chen; Hanyang Gu (Annals of Nuclear Energy, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Metabolic profile changes of zebrafish larvae in the single- and co-exposures of microplastics and phenanthrene - Jingyi Li; Xiao Liu; Jing Fu; Zhiyuan Gong; Sabrina Yanan Jiang; J. Paul Chen (Science of The Total Environment, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Efficient degradation of ciprofloxacin by innovative VUV/BN system: Kinetics, mechanism and toxicity assessment - Hongda Zhan; Zili Lin; Lingrong Chen; Zhenjun Xiao; Dezhu Liu; Yishun Wang; Zhihong Chen; Zhenchao Li; Zengkai Fu; Linsheng Liu; Zihong Xu; Shuyue Chen; et al. (Journal of Water Process Engineering, 2024)

Influences of released humic acids during thermal hydrolysis on sludge anaerobic digestion: New insights from the molecular weight of humic acids - Yaya Sun; Hongbo Liu; Jiaxin Wen; Hang Xiao; Mingze Shi; Xinlei Lu; Kai Shen; Xuedong Zhang; Bo Fu; Minhua Cui; Yajie Li; Salma Tabassum; et al. (Journal of Environmental Management, 2024)

A novel method for evaluating stability and mechanism of flexural toppling based on energy conservation principle and numerical simulation - Leilei Jin; Wenxi Fu; Yang Wang; Qianfeng Xiao; Yajing Li; Fei Ye (International Journal of Rock Mechanics and Mining Sciences, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

A comprehensive study on the impacts of thermal comfort on occupants’ thermophysiology and cognitive performances in a radiant cooling environment using physiological measurements - Shanshan Li; Yanxue Li; Weijun Gao; Fu Xiao (Energy and Buildings, 2024)

A skin-inspired anisotropic multidimensional sensor based on low hysteresis organohydrogel with linear sensitivity and excellent robustness for directional perception - Shengnan Li; Zibo Xiao; Hailong Yang; Canjie Zhu; Guoqi Chen; Jingxia Zheng; Jiayuan Ren; Wenquan Wang; Yang Cong; Luqman Ali Shah; Jun Fu (Chemical Engineering Journal, 2024)

Programmed DNA tile response system enabled accurate detection of ATP for clinical diagnosis - Dongxia Li; Yanan Peng; Liangqing Lu; Delun Chen; Bingrong Wang; Qiumei Pu; Qionglin Zhou; Xinxin Xiao; Mingpeng Fu; Xiaohong Wang; Jinchun Tu; Hua Pei; et al. (Chemical Engineering Journal, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Low-grade systemic inflammation links heavy metal exposures to mortality: A multi-metal inflammatory index approach - Yin Wang; Yuyan Wang; Ruizhen Li; Baiwen Ni; Ruixin Chen; Yun Huang; Rongrong Cheng; Pei Li; Han Li; Yang Peng; Xue Chen; Jingyu Wang; et al. (Science of The Total Environment, 2024)

Anti-inflammatory and cytotoxicity nitrogenous merosesquiterpenoids from the sponge Pseudoceratina purpurea - Xiaoli Yu; Xiao Han; Yue Mi; Yongpeng Cui; Anran Fu; Kun Liu; Xiaobin Li; Xuli Tang; Guoqiang Li (Phytochemistry, 2024)

Cytotoxic steroidal glycosides from Paris rugosa rhizomes - Jian-Ke Jia; Jun Yang; Xing-Zhi Yang; Ji-Feng Luo; Xiao-Yan Duan; Ying-Li Yang; Jin-Fu Wan; Yue-Hu Wang (Phytochemistry Letters, 2024)

A new strategy for colorimetric detection and removal of butyl xanthate in mineral processing wastewater: Based on a novel nanozyme of Ag@Fe3O4-MnO2 - Kaifeng Duan; Xin Zhao; Xi Chen; Jiangpeng Fu; Qingwei Li; Xiao Zhang; Chuanjun Zheng; Ziming Xin; Zhongtian Fu; Xiaoyu Han; Yang Wang; Cuixia Yang (Journal of Environmental Chemical Engineering, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Anti-Z-scheme polymer/polymer heterojunctions achieving synchronous enhancement of light absorption and directly spatial charge separation - Yong Li; Xinjia Zhang; Jianhua Zheng; Tianyuan Xiao; Qiu Fu; Can Yang; Dongting Wang; Guoqiang Zhang (Chemical Engineering Journal, 2024)

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Refractory COD removal from bio-treated paper wastewater using powdered activated coke adsorption technology with ozonation regeneration: Performance and molecular insights - Ying An; Huimin Zhang; Li Fu; Chen Tang; Mengyu Wang; Yunxin Xing; Fuqiang Xu; Xiao Sun; Zhen Zhou (Chemosphere, 2024)

Mitochondrial DNA copy number mediated the associations between perfluoroalkyl substances and breast cancer incidence: A prospective case-cohort study - Yue Feng; Yingqian You; Mengying Li; Xin Guan; Ming Fu; Chenming Wang; Yang Xiao; Meian He; Huan Guo (Science of The Total Environment, 2024)

Unveiling the hidden dynamics of intermittent surface water: A remote sensing framework - Zhen Xiao; Runkui Li; Mingjun Ding; Panli Cai; Jingxian Guo; Haiyu Fu; Xiaoping Zhang; Xianfeng Song (Remote Sensing of Environment, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Energy efficiency measures towards decarbonizing Japanese residential sector: Techniques, application evidence and future perspectives - Xiaoyi Zhang; Yanxue Li; Fu Xiao; Weijun Gao (Energy and Buildings, 2024)

Permanent displacement limit analysis of jointed rock slope under the near-fault pulse-like ground motion based on the rotational − translational combined failure model and tensile strength cutoff - Dejian Li; Hekai Li; Junwen Fu; Qiangshan Yu; Yingbin Zhang; Xiao Cheng (Computers and Geotechnics, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Surface free radicals activated CoP/MoS2 sensors through electrocatalytic water splitting for enhanced NO2 sensing at room temperatures - Xixi Li; Xiao Wang; Zhaokun Sun; Feifei Li; Yao Fu; Keyang Zhao; Gang Zhao; Cunguang Zhu; Xijin Xu (Chemical Engineering Journal, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

The gut microbiome: an important role in neurodegenerative diseases and their therapeutic advances - Songlin Li; Linna Zhao; Jie Xiao; Yuying Guo; Rong Fu; Yunsha Zhang; Shixin Xu (Molecular and Cellular Biochemistry, 2024)

Reclassification of Streptomyces violarus (Artamonova and Krassilnikov 1960) Pridham 1970 as a Later Heterotypic Synonym of Streptomyces violaceus (Rossi Doria 1891) Waksman 1953 using a Polyphasic Approach - Pei-Lan Long; Yin-Feng Wang; Li Fu; Yan Xiao; Shan-Guang Tang; Jian Gao (Current Microbiology, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Numerical study of the effect of helical fuel rod geometry on single-phase flow and heat transfer characteristics - Junsen Fu; Junlong Li; Ziming Wang; Tenglong Cong; Hui Guo; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2024)

Ultrasound probe enhanced enzymatic hydrolysis for rapid separation of β2-adrenergic agonists from animal urine and livestock wastewater: Applicability to biomonitoring investigation - Zhiming Xiao; Yinji Jin; Ying Cao; Ting Yao; Yao Fu; Decheng Suo; Shi Wang; Gang Chen; Xinxue Zhao; Runxian Li; Xia Fan (Analytica Chimica Acta, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Dynamics of green macroalgal micro-propagules and the influencing factors in the southern Yellow Sea, China - Xiaojun Ma; Xiaoxiang Miao; Shiliang Fan; Yu Zang; Baotang Zhang; Mei Li; Xuelei Zhang; Mingzhu Fu; Zongling Wang; Jie Xiao (Science of The Total Environment, 2024)

Occurrence, distribution characteristics and exposure assessment of perchlorate in the environment in China - Diancheng Dou; Ming He; Jinxin Liu; Shumin Xiao; Fu Gao; Wei An; Li Qi (Journal of Hazardous Materials, 2024)

Microplastic pollution differences in freshwater river according to stream order: Insights from spatial distribution, annual load, and ecological assessment - Weikeng Luo; Hongyu Fu; Qiyuan Lu; Bowen Li; Xue Cao; Sifan Chen; Ruijuan Liu; Bin Tang; Xiao Yan; Jing Zheng (Journal of Environmental Management, 2024)

Preparation of functional oils rich in phytosterol esters and diacylglycerols by enzymatic transesterification - Wangxu Shi; Houyue Li; Yijie Fu; Xiao Tang; Junwen Yu; Xiaosan Wang (Food Chemistry, 2024)

Discrimination and prediction of Qingzhuan tea storage year using quantitative chemical profile combined with multivariate analysis: Advantages of MRMHR based targeted quantification metabolomics - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Evaluation of potential prebiotic activity of a novel fucose-containing trisaccharide prepared from bacterial exopolysaccharides - Mengshi Xiao; Jiayuan Bi; Xinmiao Ren; Xiaodan Fu; Dongyu Li; Rong Li; Haijin Mou (Food Bioscience, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Stochastic occupancy modeling for spaces with irregular occupancy patterns using adaptive B-Spline-based inhomogeneous Markov Chains - Hanbei Zhang; Christian Ankerstjerne Thilker; Henrik Madsen; Rongling Li; Fu Xiao; Tianyou Ma; Kan Xu (Building and Environment, 2024)

Sensitivity of atmospheric peroxyacetyl nitrate (PAN) formation and its impact on ozone pollution in a coastal city - Nan Fu; Li-Ming Cao; Shi-Yong Xia; Le-Wei Zeng; Li He; Ling-Yan He; Xiao-Feng Huang (Atmospheric Environment, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Role of ginsenoside Rb1 in attenuating depression-like symptoms through astrocytic and microglial complement C3 pathway - Cheng-Fu Li; Qiu-Ping Zhang; Jie Cheng; Guang-Hui Xu; Ji-Xiao Zhu; Li-Tao Yi (Metabolic Brain Disease, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Reproducing surface water isoscapes of δ18O and δ2H across China: A machine learning approach - Huawu Wu; Hongxiang Fan; Jing Li; Fu-Jun Yue; Ergang Lian; Congsheng Fu; Ruiyu Lei; Mengyao Ding; Jinzhao Liu; Xiao-Yan Li (Journal of Hydrology, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Molecular organic geochemistry and origin of oil in the Potwar Basin, Pakistan - Sajjad Ali; Meijun Li; Jian Fu; Asghar A.A.D. Hakro; Hong Xiao; Xiaolin Lu; Rizwan Sarwar Awan; Dongyong Wang (Journal of Asian Earth Sciences, 2024)

Coupling and coordination of rainfall erosivity and aerosols in the Pearl River Basin under multiple shared socio-economic pathways - Zhen Cao; Dayun Zhu; Yingshan Zhao; Hua Xiao; Ronghan Li; Linjing Fu (Theoretical and Applied Climatology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Potential risk assessment of the large hydropower station dumpsite using numerical simulation: a case study in Shanxi Province, China - Dong-dong Li; Han-dong Liu; Zhong-fu Wang; Feng-lan Chen; Xiao-chao Li (Natural Hazards, 2024)

Microstrip isoelectric focusing with deep learning for simultaneous screening of diabetes, anemia, and thalassemia - Haodong Fu; Youli Tian; Genhan Zha; Xuan Xiao; Hengying Zhu; Qiang Zhang; Changjie Yu; Wei Sun; Chang Ming Li; Li Wei; Ping Chen; Chengxi Cao (Analytica Chimica Acta, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Developing an Artificial Intelligence-Based Method for Predicting the Trajectory of Surface Drifting Buoys Using a Hybrid Multi-Layer Neural Network Model - Miaomiao Song; Wei Hu; Shixuan Liu; Shizhe Chen; Xiao Fu; Jiming Zhang; Wenqing Li; Yuzhe Xu (Journal of Marine Science and Engineering, 2024)
Accurately predicting the long-term trajectory of a surface drifting buoy (SDB) is challenging. This paper proposes a promising solution to the SDB trajectory prediction based on artificial intelligence (AI) technologies. Initially, a scalable mathematical model for trajectory prediction is developed, transforming the challenge of predicting trajectory points into predicting velocities in eastward and northward directions. Subsequently, a four-layer trajectory prediction calculation framework (FLTPCF) is established, outlining a complete workflow for the real-time online training of marine environment data and SDBs’ trajectory prediction. Thirdly, for facilitating accurate long-term trajectory prediction, a hybrid artificial neural network trajectory prediction model, named CNN–BiGRU–Attention, integrates a Convolutional Neural Network (CNN), Bidirectional Gated Recurrent Unit (BiGRU), and Attention mechanism (AM), tuned for spatiotemporal feature extraction and extended time-series reasoning. Extensive experiments, including ablation studies, comparative analyses with state-of-the-art models like BiLSTM and Transformer, evaluations against numerical methods, and adaptability tests, were conducted for justifying the CNN–BiGRU–Attention model. The results highlight the CNN–BiGRU–Attention model’s excellent convergence, accuracy, and generalization capabilities in predicting 24, 48, and 72 h trajectories for SDBs with varying drogue statuses and under different sea conditions. This work has great potential to promote the intelligent degree of marine environmental monitoring.

Ocean eddy detection based on YOLO deep learning algorithm by synthetic aperture radar data - Nannan Zi; Xiao-Ming Li; Martin Gade; Han Fu; Sisi Min (Remote Sensing of Environment, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Elevated nitrogen loadings facilitate carbon dioxide emissions from urban inland waters - Yong-Mei Hou; Fu-Jun Yue; Si-Liang Li; Xiao-Long Liu (Journal of Environmental Management, 2024)

Preparation, structural characterization and rheological properties of a novel fucose-containing exopolysaccharide from Clavibacter michiganensis - Mengshi Xiao; Luying Tang; Xiaodan Fu; Xinmiao Ren; Jiayuan Bi; Jia Wang; Dongyu Li; Qing Kong; Haijin Mou; Changliang Zhu (Food Hydrocolloids, 2024)

Insights into synergetic modulation of nickel sites over graphene by introducing tungsten and light for efficient methanol electrooxidation - He Xiao; Wenxiang Wang; Man Zhao; Zimei Fu; Meng Bai; Li Zhang; Junming Zhang; Ergui Luo; Jian Zhang; Haishun Wu; Jianfeng Jia (Chemical Engineering Journal, 2024)

Tryptophan catabolism via the kynurenine pathway regulates infection and inflammation: from mechanisms to biomarkers and therapies - Jingpu Zhang; Yanlei Liu; Xiao Zhi; Li Xu; Jie Tao; Daxiang Cui; Tie Fu Liu (Inflammation Research, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Elucidation of the dominant factors influencing N2O emission in water-level fluctuation zones in a karst canyon reservoir, southwest China - Sai-Nan Chen; Yongmei Hou; Fu-Jun Yue; Zhifeng Yan; Xiao-Long Liu; Si-Liang Li (Science of The Total Environment, 2024)

Salt dynamic changes between seawater and phreatic brine in muddy tidal flats under tidal influence - Yufeng Zhang; Xiaoteng Xiao; Zengbing Sun; Bingxiao Lei; Mingbo Li; Xiujun Guo; Tengfei Fu; Cheng Xing (Journal of Hydrology, 2024)

Interfacial OOH* mediated Fe(II) regeneration on the single atom Co-N-C catalyst for efficient Fenton-like processes - Bao-Gang Fu; Xiangtong Zhou; Yilin Lu; Wen-Zhu Quan; Chunmei Li; Liang Cheng; Xiang Xiao; Yang-Yang Yu (Journal of Hazardous Materials, 2024)

Recent development of carrier materials in anthocyanins encapsulation applications: A comprehensive literature review - Ze Fu; Hao Ju; Guang-Sen Xu; Yan-Chao Wu; Xiao Chen; Hui-Jing Li (Food Chemistry, 2024)

Lemon essential oil nanoemulsions: Potential natural inhibitors against Escherichia coli - Wenbin Xiao; Zhipeng Gao; Ting Liu; Weiming Zhong; Sifan Jiang; Mingwang He; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Microbiology, 2024)

Lightning activity and microphysical structure characteristics during the convective cell mergers in an extreme mesoscale convective system - Jing Sun; Yanjiao Xiao; Yunying Li; Muyun Du; Zhikang Fu; Liang Leng; Ran Cai; Haopeng Wu (Atmospheric Research, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Deep leaning in food safety and authenticity detection: An integrative review and future prospects - Yan Wang; Hui-Wen Gu; Xiao-Li Yin; Tao Geng; Wanjun Long; Haiyan Fu; Yuanbin She (Trends in Food Science & Technology, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Characterization of organic vapors by a Vocus proton-transfer-reaction mass spectrometry at a mountain site in southeastern China - Yi Zhang; Weiqi Xu; Wei Zhou; Yan Li; Zijun Zhang; Aodong Du; Hongqin Qiao; Ye Kuang; Lanzhong Liu; Zhiqiang Zhang; Xiao He; Xueling Cheng; et al. (Science of The Total Environment, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Indole-3-carboxaldehyde alleviates cisplatin-induced acute kidney injury in mice by improving mitochondrial dysfunction via PKA activation - Peipei Yuan; Aozi Feng; Yaxin Wei; Saifei Li; Yang Fu; Xiao Wang; Menghuan Guo; Weisheng Feng; Xiaoke Zheng (Food and Chemical Toxicology, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Bioinspired breathable biodegradable bioelastomer-based flexible wearable electronics for high-sensitivity human-interactive sensing - Chenlin Huang; Mingyue Xiao; Zehui Li; Zihong Fu; Rui Shi (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Polycyclic aromatic compounds (PACs) in industrial soils from northwestern of China: occurrence, distribution, exposure risk, and implications on risk-based controls - Yousong Zhou; Kai Xiao; Yongqiang Zhang; Donglei Fu; Ke Jiang; Jinmu Luo; Yuancheng Li; Guofeng Shen; Wenxin Liu; Shu Tao; Senlin Lu (Environmental Geochemistry and Health, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Unravelling bioaccumulation, depletion and metabolism of organophosphate triesters in laying hens: Insight of in vivo biotransformation assisted by diester metabolites - Yuhan Yin; Nannan Zhao; Wenxiao Pan; Qiao Xue; Jie Fu; Zhiming Xiao; Ruiguo Wang; Peilong Wang; Xiaomin Li (Journal of Hazardous Materials, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Micro formation mechanism of oil–water inversion in reservoirs based on water film theory—An example from the Dawangzhuang Oilfield in Bohai Bay Basin - Xiao Hu; Longchuan Pu; Aihua Ran; Jun Xie; Fengqun Li; Yuzong Cheng; Suhua Zhang; Zhe Li; Qiongyao Pu; Jialin Fu (Fuel, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Evaluating the potential of different bioaugmented strains to enhance methane production during thermophilic anaerobic digestion of food waste - Na Wang; Mengyao Xiao; Siying Zhang; Xiaomiao Chen; Jingjing Shi; Shanfei Fu; Jiping Shi; Li Liu (Environmental Research, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Constructing light-insensitive Ag(I) sites by in situ integration of nanoheaters for efficient adsorptive desulfurization - Jun Liu; Zhen Fu; Peng Tan; Min Li; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

αExtractor: a system for automatic extraction of chemical information from biomedical literature - Jiacheng Xiong; Xiaohong Liu; Zhaojun Li; Hongzhong Xiao; Guangchao Wang; Zhenjiang Niu; Chaoyuan Fei; Feisheng Zhong; Gang Wang; Wei Zhang; Zunyun Fu; Zhiguo Liu; et al. (Science China Life Sciences, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

Stability analysis of intermittently jointed rock slopes based on the stepped failure mode - Dejian Li; Junwen Fu; Hekai Li; Xiao Cheng; Lianheng Zhao; Yingbin Zhang; Xinyan Peng (Journal of Mountain Science, 2024)

Comparison of leaf chlorophyll content retrieval performance of citrus using FOD and CWT methods with field-based full-spectrum hyperspectral reflectance data - Bin Xiao; Sunzhe Li; Shiqing Dou; Hongchang He; Bolin Fu; Tengxu Zhang; Weiwei Sun; Yanli Yang; Yuankang Xiong; Jinke Shi; Jie Zhang (Computers and Electronics in Agriculture, 2024)

Bisphenol analogues in infant foods in south China and implications for infant exposure - Quanzhi Zheng; Jinqiu Xiao; Duo Zhang; Xiangyu Li; Jiayi Xu; Jiaojiao Ma; Qinru Xiao; Jinfeng Fu; Zhihui Guo; Yue Zhu; Jiajia Ji; Shaoyou Lu (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Homoerythrina-type alkaloids with neuroprotective activity from the branches of Cephalotaxus hainanensis Li - Hao Yan; Hao Wang; Peng-Wei Chen; Li Yang; Hui-Qin Chen; Fei Wu; Pei Wang; Hao-Fu Dai; Xiao-Long Huang; Shuang-Qing Zhou; Wen-Li Mei (Phytochemistry Letters, 2024)

Gravity driven membrane bioreactor simulates the effect of permeable brick on pollution reduction of rainwater runoff in Low Impact Development (LID) - Xiao Ma; Zhenhao Liang; Jiawan Li; Caixia Fu; Wei Song; Xing Du; Yu Zhou; Feng Liu (Journal of Water Process Engineering, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

Experimental investigation of mold growth risk among typical residential indoor materials: Case study in coastal city, China - Jiuli Qiao; Xiaoyi Zhang; Fu Xiao; Yanxue Li; Weijun Gao (Energy and Buildings, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Species pool, local assembly processes: Disentangling the mechanisms determining bacterial α‐ and β‐diversity during forest secondary succession - Xiao Zhang; Handan Dai; Yongtao Huang; Kuan Liu; Xingang Li; Shuoxin Zhang; Shenglei Fu; Shuo Jiao; Chunbo Chen; Biao Dong; Zhu Yang; Yang Cui; et al. (Molecular Ecology, 2024)
Across ecology, and particularly within microbial ecology, there is limited understanding how the generation and maintenance of diversity. Although recent work has shown that both local assembly processes and species pools are important in structuring microbial communities, the relative contributions of these mechanisms remain an important question. Moreover, the roles of local assembly processes and species pools are drastically different when explicitly considering the potential for saturation or unsaturation, yet this issue is rarely addressed. Thus, we established a conceptual model that incorporated saturation theory into the microbiological domain to advance the understanding of mechanisms controlling soil bacterial diversity during forest secondary succession. Conceptual model hypotheses were tested by coupling soil bacterial diversity, local assembly processes and species pools using six different forest successional chronosequences distributed across multiple climate zones. Consistent with the unsaturated case proposed in our conceptual framework, we found that species pool consistently affected α‐diversity, even while local assembly processes on local richness operate. In contrast, the effects of species pool on β‐diversity disappeared once local assembly processes were taken into account, and changes in environmental conditions during secondary succession led to shifts in β‐diversity through mediation of the strength of heterogeneous selection. Overall, this study represents one of the first to demonstrate that most local bacterial communities might be unsaturated, where the effect of species pool on α‐diversity is robust to the consideration of multiple environmental influences, but β‐diversity is constrained by environmental selection.

The two salinity peaks mode of marine salt supply to coastal underground brine during a single tidal cycle - Xiaoteng Xiao; Yufeng Zhang; Tengfei Fu; Zengbing Sun; Bingxiao Lei; Mingbo Li; Xiujun Guo (Frontiers in Marine Science, 2024)
Seawater salt is constantly supplied from the marine environment to coastal underground brine deposits, meaning that brine has the potential for continuous extraction. There is currently a lack of information about the processes that drive the fluxes of seawater salt to underground brine deposits in tidal-driven brine mining areas. We chose the Yangkou salt field on the southern coast of Laizhou Bay, a brine mining area, as our study site. We monitored the spatial and temporal distribution of the underground brine reserve and the changes in water level and salinity in the mining area and adjacent tidal flats using electrical resistivity tomography and hydrogeological measurements. We monitored cross-sections along two survey lines and observed that the underground brine reserve receives a stable supply of seawater salt, and calculated that the rate of influx into the brine body in the mining area near the boundary of the precipitation funnel was 0.226−0.232 t/h. We calculated that a total salt flux of approximately 5.50 t enters the underground brine body every day through a 150 m long shoreline and a 1322.3 m 2 window, which is sufficient to sustain the daily extraction of one brine well. During tidal cycles, there are two peaks in the salinity of the water supplied to the underground brine reserve, which means that the brine supply is from at least two high-salinity salt sources in different tidal stages. The first salinity peak occurs during the initial stage of the rising tide after seawater inundates the tidal flat. At this time, seawater, which is a solution and carries a large amount of evaporated salt, is transported into the brine layer through highly permeable areas or biological channels and replenishes the brine in the mining area. The second salinity peak occurs during the early stage of the falling tide. Influenced by hysteresis-driven tidal pumping, high-salinity brine from the lower intertidal zone is rapidly transported into the mining area, thereby increasing the salinity of the underground brine.

Inter-relationships of obesity-related eating behavior with depression and anxiety among adults during the COVID-19 pandemic: A network analysis - Xue Wang; Yibo Wu; Li Fu; Xiao Fu; Chang Pang; Shuang Zang (Appetite, 2024)

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

The relationship of organophosphate flame retardants with hyperuricemia and gout via the inflammatory response: An integrated approach - Yuxuan Tan; Yingyin Fu; Huojie Yao; Haiying Li; Xiaomei Wu; Ziang Guo; Xiao Liang; Mincong Kuang; Lei Tan; Chunxia Jing (Science of The Total Environment, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Zinc-doped carbon quantum dots-based ratiometric fluorescence probe for rapid, specific, and visual determination of tetracycline hydrochloride - Feijiao Hu; Quanbin Fu; Yijing Li; Cuijuan Yan; Dehui Xiao; Peng Ju; Zhiyong Hu; Houshen Li; Shiyun Ai (Food Chemistry, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Outdoor artificial light at night and male sperm quality: A retrospective cohort study in China - Run Tian; Tingting Yang; Chenghan Xiao; Fuping Li; Leyao Fu; Lu Zhang; Jiarui Cai; Sixuan Zeng; Junhao Liao; Guishuang Song; Chuan Yu; Ben Zhang; et al. (Environmental Pollution, 2024)

Salt transport dynamics across the sediment-underground brine interface driven by tidal hydrology and benthic crab burrowing in muddy tidal flats - Tengfei Fu; Yufeng Zhang; Xiujun Guo; Cheng Xing; Xiaoteng Xiao; Bingxiao Lei; Zengbing Sun; Mingbo Li (Estuarine, Coastal and Shelf Science, 2024)

One-step fabrication of an injectable antibacterial collagen hydrogel with in situ synthesized silver nanoparticles for accelerated diabetic wound healing - Caihong Fu; Yirui Fan; Guangyu Liu; Wenhua Li; Jianrui Ma; Jianxi Xiao (Chemical Engineering Journal, 2024)

4-Hydroxybenzenesulfonic acid triggers rapid preparation of phenolic aerogel composites by ambient pressure drying - Xi Zhao; Lin Chen; Peng-Gang Su; Lin-Xi Xiao; Hai-Bo Zhao; Teng Fu; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Regulating the crystallinity and hydrophobicity of cobalt boride nanosheet for enhanced CO2 photoreduction performance - Xinyan Xiao; Zheyang Liu; Min Zhou; Wei Zhang; Xiaohong Fu; Huaming Li; Zhifeng Jiang (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Origin and tectonic environment of the Longbohe Fe-Cu-(LREE) deposit in the Ailao Shan–Red River shear zone, Southwest China: a Neoproterozoic subduction-related IOCG deposit? - Lei Liu; Wei Terry Chen; Xiao-Chun Li; Xin-Fu Zhao (Mineralium Deposita, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Climate and mineral accretion as drivers of mineral‐associated and particulate organic matter accumulation in tidal wetland soils - Chuancheng Fu; Yuan Li; Lin Zeng; Chen Tu; Xiaoli Wang; Haiqing Ma; Leilei Xiao; Peter Christie; Yongming Luo (Global Change Biology, 2024)
Tidal wetlands sequester vast amounts of organic carbon (OC) and enhance soil accretion. The conservation and restoration of these ecosystems is becoming increasingly geared toward “blue” carbon sequestration while obtaining additional benefits, such as buffering sea‐level rise and enhancing biodiversity. However, the assessments of blue carbon sequestration focus primarily on bulk SOC inventories and often neglect OC fractions and their drivers; this limits our understanding of the mechanisms controlling OC storage and opportunities to enhance blue carbon sinks. Here, we determined mineral‐associated and particulate organic matter (MAOM and POM, respectively) in 99 surface soils and 40 soil cores collected from Chinese mangrove and saltmarsh habitats across a broad range of climates and accretion rates and showed how previously unrecognized mechanisms of climate and mineral accretion regulated MAOM and POM accumulation in tidal wetlands. MAOM concentrations (8.0 ± 5.7 g C kg −1 ) (±standard deviation) were significantly higher than POM concentrations (4.2 ± 5.7 g C kg −1 ) across the different soil depths and habitats. MAOM contributed over 51.6 ± 24.9% and 78.9 ± 19.0% to OC in mangrove and saltmarsh soils, respectively; both exhibited lower autochthonous contributions but higher contributions from terrestrial or marine sources than POM, which was derived primarily from autochthonous sources. Increased input of plant‐derived organic matter along the increased temperature and precipitation gradients significantly enriched the POM concentrations. In contrast, the MAOM concentrations depended on climate, which controlled the mineral reactivity and mineral–OC interactions, and on regional sedimentary processes that could redistribute the reactive minerals. Mineral accretion diluted the POM concentrations and potentially enhanced the MAOM concentrations depending on mineral composition and whether the mineral accretion benefited plant productivity. Therefore, management strategies should comprehensively consider regional climate while regulating sediment supply and mineral abundance with engineering solutions to tap the OC sink potential of tidal wetlands.

Research on the effect of environmental regulation to the green water resource efficiency in China—based on the perspectives of high pressure and low suction - Zhongwen Pan; Liping Fu; Xiao xiang Li; Jingrong Li; Xinyang Li; Ying Peng; Xinlin Fu (Environmental Science and Pollution Research, 2023)

Csswin-unet: a Swin-unet network for semantic segmentation of remote sensing images by aggregating contextual information and extracting spatial information - Dong Xiao; Zhihao Kang; Yanhua Fu; Zhenni Li; Mengying Ran (International Journal of Remote Sensing, 2023)

S-scheme MOF-on-MOF heterojunctions for enhanced photo-Fenton Cr(VI) reduction and antibacterial effects - Longyang Wang; Kejie Zhang; Jianying Qian; Mengyi Qiu; Ningyi Li; Hao Du; Xiao Hu; Yangjie Fu; Meng Tan; Derek Hao; Qi Wang (Chemosphere, 2023)

Dynamic and harmonious allocation of irrigation water resources under climate change: A SWAT-based multi-objective nonlinear framework - Kaihua Cao; Xiao Liu; Qiang Fu; Yijia Wang; Dong Liu; Tianxiao Li; Mo Li (Science of The Total Environment, 2023)

Metabolomics and metatranscriptomics reveal the influence mechanism of endogenous microbe (Staphylococcus succinus) inoculation on the flavor of fermented chili pepper - Yumeng Li; Xiaoqin Luo; Huan Guo; Jinrong Bai; Yue Xiao; Yuan Fu; Yanping Wu; Hongyu Wan; Yina Huang; Hong Gao (International Journal of Food Microbiology, 2023)

Tianwen-1 and MAVEN observations of Martian oxygen ion plumes - Xiao Ma; Anmin Tian; Ruilong Guo; Lihui Chai; Quanqi Shi; Shichen Bai; Qiugang Zong; Linggao Kong; Wenya Li; Binbin Tang; Aibing Zhang; Suiyan Fu; et al. (Icarus, 2023)

Lidocaine pretreatment attenuates inflammatory response and protects against sepsis-induced acute lung injury via inhibiting potassium efflux-dependent NLRP3 activation - Kai Su; Xin-Tao Li; Fang-Xiao Hong; Mu Jin; Fu-Shan Xue (Inflammation Research, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Chidamide inhibits cell glycolysis in acute myeloid leukemia by decreasing N6-methyladenosine-related GNAS-AS1 - Changmei Hu; Xiao Fu; Shujun Li; Cong Chen; Xielan Zhao; Jie Peng (DARU Journal of Pharmaceutical Sciences, 2023)

Maximum helical dichroism enabled by an exceptional point in non-Hermitian gradient metasurfaces - Xiao Li; Chuanjie Hu; Yuan Tian; Youwen Liu; Huanyang Chen; Yadong Xu; Ming-Hui Lu; Yangyang Fu (Science Bulletin, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Carbonate lithium isotope systematics indicate cooling triggered mass extinction during the Frasnian-Famennian transition - Yang-Yang Wang; Kun Liang; Yilin Xiao; Bo Chen; Erhao Shan; Tingyu Yang; Meng Zhang; He Sun; Hai-Ou Gu; Fengtai Tong; Lulu Fu; Dong-Yong Li; et al. (Global and Planetary Change, 2023)

Revealing the chemical differences and their application in the storage year prediction of Qingzhuan tea by SWATH-MS based metabolomics analysis - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Dan Zou; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Plume effects on Martian surface: Revealing evolution characteristics of plume-surface interaction at Tianwen-1 landing site - Pengwei Luo; Xiaoping Zhang; Renrui Liu; Mingjie Zhang; Cunhui Li; Yi Xu; Roberto Bugiolacchi; Baocheng Hua; Haiyan Zhang; Liansheng Li; Jilin You; Yanyan Xu; et al. (Engineering Geology, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

Invasive Asteraceae plants can enhance community stability by changing pollination network structure, yet cause intense pollen disturbance to native plants in an oceanic island community - Xiang-Ping Wang; Xiao Fu; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Biological Invasions, 2023)

Current advances in the detection and removal of organic arsenic by metal-organic frameworks - Wen-Qing Ding; Lazhar Labiadh; Lei Xu; Xiao-Ying Li; Chen Chen; Ming-Lai Fu; Baoling Yuan (Chemosphere, 2023)

Topology optimization on the attenuation degree of evanescent waves in periodic pile barriers - Xiao Wang; Shui Wan; Peng Zhou; Jundong Fu; Shuli Li (Soil Dynamics and Earthquake Engineering, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

Trace elements and Li isotopes distinguish between liquid and solid phases contributing to mafic arc magmas - Li-Tao Ma; Li-Qun Dai; Yong-Fei Zheng; Zi-Fu Zhao; Bing Gong; Yilin Xiao; Fengtai Tong (Lithos, 2023)

Investigation on microscopic forces between methane hydrate particles in gas phase dominated system - Pengfei Li; Shikun Tong; Jihao Pei; Jianbo Zhang; Yukun Guo; Xiao Liu; Weiqi Fu; Zhiyuan Wang (Fuel, 2023)

Loading rate effect on the strength of granular material considering particle rotation - Lihong Tong; Li Fu; Changjie Xu; Haibin Ding; Min Xiao (Computers and Geotechnics, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Diode effects on street canyon ventilation in valley city: Temperature inversion and calm geostrophic wind - Jin Shang; Huai-Yu Zhong; Hong-Liang Zhang; Bin Li; Xiao-Xue Wang; Fu-Yun Zhao; Yuguo Li (Building and Environment, 2023)

Experimental analysis and two-region mixing coefficients development for a wire-wrapped tight lattice bundle - Junlong Li; Yao Xiao; Junsen Fu; Qi Zhang; Zhenqin Xiong; Hanyang Gu (Annals of Nuclear Energy, 2023)

Effects of Weight Gain During Pregnancy in Normal-Weight Women on Changes in the Gut Microbiota of Pregnant Women in the Third Trimester - Fengping Fu; Fengqin Wang; Jian Ding; Li Xiao; Xia Song (Biochemical Genetics, 2023)

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Reduction potential of vehicular emission in Chengdu, China: A case study of COVID-19 - Xinping Yang; Hefeng Zhang; Wei Li; Hong Tian; Yongdong Wang; Jing Zhou; Ze Bao; Xiaorui Chen; Teng Xiao; Yunjing Wang; Mingliang Fu; Xian Wu; et al. (Urban Climate, 2023)

Mechanism of microbial inhibition of rainfall erosion in black soil area, as a soil structure builder - Zhaoxing Xiao; Renjie Hou; Tianxiao Li; Fanxiang Meng; Qiang Fu; Mo Li; Dong Liu; Yi Ji; Shuqi Dong (Soil and Tillage Research, 2023)

Seasonal variation characteristics of atmospheric peroxyacetyl nitrate (PAN) and its source apportionment in a megacity in southern China - Shi-Yong Xia; Xiao-Feng Huang; Zhi-Jie Li; Nan Fu; Zhen Jiang; Li-Ming Cao; Le-Wei Zeng; Guang-He Yu (Science of The Total Environment, 2023)

Identification and contribution of potential sources to atmospheric lead pollution in a typical megacity: Insights from isotope analysis and the Bayesian mixing model - Wen-Jing Dai; Xiao-Dong Li; Yu-Cong Fu; Shi-Yuan Ding; Qin-Kai Li; Zhi-Qi Zhao (Science of The Total Environment, 2023)

Characteristics of persulfate gel materials in groundwater remediation: Column and tank experiments investigations - Yu Yang; Xiangjian Xu; Fu Xia; Shuoyang Wan; Xu Han; Han Xiao; Sheng Deng; Yonghai Jiang; Xiang Li (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Simulation of Rayleigh convection during dichloromethane absorption by water using lattice Boltzmann method - Ruixue Xiao; Kefan Chao; Ju Liu; Li Wang; Muhua Chen; Xinbao Zhu; Bo Fu (Process Safety and Environmental Protection, 2023)

Dictamnine suppresses the development of pear ring rot induced by Botryosphaeria dothidea infection by disrupting the chitin biosynthesis - Minxuan Yuan; Xiaogui Liang; Duantao Cao; Hongliang Wu; Suling Xiao; Hui Liang; Hang Li; Yingjin Huang; Hongyi Wei; Wenwen Peng; Xiaoxiang Fu (Pesticide Biochemistry and Physiology, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

Structural characterization of a novel fucosylated trisaccharide prepared from bacterial exopolysaccharides and evaluation of its prebiotic activity - Mengshi Xiao; Xinmiao Ren; Jiaying Cheng; Xiaodan Fu; Rong Li; Changliang Zhu; Qing Kong; Haijin Mou (Food Chemistry, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Energy-oriented control retrofit for existing HVAC system adopting data-driven MPC – Methodology, implementation and field test - Bao Yue; Bing Su; Fu Xiao; Anbang Li; Kehua Li; Shen Li; Rui Yan; Qiuzhuang Lian; Ao Li; Yuanyang Li; Xing Fang; Xingang Liang (Energy and Buildings, 2023)

Investigation of p-n sensing transition and related highly sensitive NH3 gas sensing behavior of SnPx/rGO composites - Yao Fu; Tongkai Wang; Xiao Wang; Xixi Li; Yuli Zhao; Feifei Li; Gang Zhao; Xijin Xu (Chemical Engineering Journal, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

An advanced treatment process for 3-high wastewater discharged from crude oil storage tanks - Xue-Wen Li; Zhong-Yi Cui; Bao-Fu Zhao; Jin-An Wang; Yue-Qin Song; Xiao-Long Zhou (Environmental Science and Pollution Research, 2023)

Co-exposure to parabens and triclosan and associations with cognitive impairment in an elderly population from Shenzhen, China - Xiaohu Ren; Yilan Deng; Wei Liu; Jinfeng Fu; Zhihong Huang; Duo Zhang; Qinru Xiao; Xiangyu Li; Xiao Chen; Xinfeng Huang; Jianjun Liu; Shaoyou Lu (Chemosphere, 2023)

Design method of combined stiffened pressure hulls with variable-curvature characteristic - Xiao Fu; Zhiyuan Mei; Shuo Wang; Xuefei Bai; Er Zhang; Guotao Chen; Huadong Li (Ocean Engineering, 2023)

Metagenome-based analysis of carbon-fixing microorganisms and their carbon-fixing pathways in deep-sea sediments of the southwestern Indian Ocean - Xiao-Lan Yue; Lin Xu; Li Cui; Ge-Yi Fu; Xue-Wei Xu (Marine Genomics, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Research progress and applications of colorful Brassica crops - Fuyan Li; Yingying Gong; Annaliese S. Mason; Qian Liu; Juan Huang; Miao Ma; Meili Xiao; Huadong Wang; Donghui Fu (Planta, 2023)

Distinct resting-state functional connectivity patterns of Anterior Insula affected by smoking in mild cognitive impairment - Tianyi Zhang; Qingze Zeng; Kaicheng Li; Xiaocao Liu; Yanv Fu; Tiantian Qiu; Peiyu Huang; Xiao Luo; Zhirong Liu; Guoping Peng (Brain Imaging and Behavior, 2023)
Smoking is a modifiable risk factor for Alzheimer’s disease (AD). The insula plays a vital role in both smoking and cognition. However, the smoking effects on insula-related networks in cognitively normal controls (CN) and mild cognitive impairment (MCI) patients remain unknown. We identified 129 CN (85 non-smokers and 44 smokers) and 83 MCI (54 non-smokers and 29 smokers). Each underwent neuropsychological assessment and MRI (structural and resting-state functional). Seed-based functional analyses in the anterior and posterior insula were performed to calculate the functional connectivity (FC) with voxels in the whole brain. Mixed-effect analyses were performed to explore the interactive effects on smoking and cognitive status. Associations between FC and neuropsychological scales were assessed. Mixed-effect analyses revealed the FC differences between the right anterior insula (RAI) with the left middle temporal gyrus (LMTG) and that with the right inferior parietal lobule (RIPL) ( p < 0.01, cluster level < 0.05, two-tailed, gaussian random field correction). The FC of RAI in both LMTG and RIPL sees a significant decrease in MCI smokers ( p < 0.01). Smoking affects insula FC differently between MCI and CN, and could decrease the insula FC in MCI patients. Our study provides evidence of neural mechanisms between smoking and AD.

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Influence of the catching dam layout on the kinematic characteristics of rock avalanche - Dong-dong Li; Han-dong Liu; Zhong-fu Wang; Xiao-chao Li (Natural Hazards, 2023)

Scutellarin prevents acute alcohol-induced liver injury via inhibiting oxidative stress by regulating the Nrf2/HO-1 pathway and inhibiting inflammation by regulating the AKT, p38 MAPK/NF-κB pathways - Xiao Zhang; Zhicheng Dong; Hui Fan; Qiankun Yang; Guili Yu; Enzhuang Pan; Nana He; Xueqing Li; Panpan Zhao; Mian Fu; Jingquan Dong (Journal of Zhejiang University-SCIENCE B, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Complete genome sequence of Bacillus cereus 2-6A, a marine exopolysaccharide-producing bacterium isolated from deep-sea hydrothermal sediment of the Pacific Ocean - Xuan Zou; Chuan-Lei Suo; Xiao-Mei Geng; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Peng Wang; Mei-Ling Sun (Marine Genomics, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

A nationwide investigation of trace elements in rice and wheat flour in China: Levels, spatial distributions and implications for human exposure - Xiangyu Li; Fu Wang; Xiaoling Feng; Qinru Xiao; Quanzhi Zheng; Jiayi Xu; Jiaojiao Ma; Jiajia Ji; Shaoyou Lu (Environmental Science and Pollution Research, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Ligand-binding properties of chemosensory protein 1 in Callosobruchus chinensis to mung bean volatiles - Qiang Liu; Mao-Zhu Yin; Sai Ma; Nan Gu; Li-Fu Qian; Ya-Nan Zhang; Xiao-Ming Li (Pesticide Biochemistry and Physiology, 2023)

Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles - Ke Zhang; Qing Chen; Jie Xiao; Lijun You; Siming Zhu; Chao Li; Xiong Fu (Food Hydrocolloids, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

A review and reflection on open datasets of city-level building energy use and their applications - Xiaoyu Jin; Chong Zhang; Fu Xiao; Ao Li; Clayton Miller (Energy and Buildings, 2023)

Free energy regulation and domain engineering of BaTiO3-NaNbO3 ceramics for superior dielectric energy storage performance - Wenrong Xiao; Zhen Liu; Chao Zhang; Zhanming Dou; Baoyan Fan; Meng Shen; Ying Yang; Wei Luo; Kanghua Li; Qiuyun Fu; Shenglin Jiang; Yaojin Wang; et al. (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

How do montane plants manage to survive? Inferring from non-structural carbohydrates - Wensheng Chen; Huihui Ding; Jiangrong Li; Fangwei Fu; Yueyao Li; Siying Xiao; Di Xu; Jie Lu; Jiangping Fang (Trees, 2023)

New hydrous phases in the Al2O3-SiO2-H2O system under the mantle transition zone conditions - Baoyun Wang; Jin Liu; Suyu Fu; Pu Xiao; Li Li; Xing Ding; Wansheng Xiao (Science China Earth Sciences, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Determination of nitrogen sources and losses in surface runoff from different lands at a watershed scale - Zanfang Jin; Jiazheng Xiao; Hongyu Ye; Guowei Fu; Guangyao Li; Wangbin Wu; Feili Li (Environmental Science and Pollution Research, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

A linkage between early Silurian Nb-REE enriched alkaline magmatism and Neoproterozoic subduction metasomatized mantle in South Qinling, Central China - Jian-Hui Su; Xin-Fu Zhao; Xiao-Chun Li; Sheng-Ren Chang; Yuan-Bao Wu; Carl Spandler (Lithos, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

First Asian fossil record of Platydictya (Amblystegiaceae) from the lower Miocene and its paleoenvironmental significance - Liyan Guo; Liang Xiao; Ya Li; Xiangchuan Li; Qin Leng; Nan Sun; Junfeng Guo; Chaofeng Fu; Jianan Wang; Deshuang Ji (Frontiers of Earth Science, 2023)

Strontium isotopes in the Ordovician paleokarst reservoirs, Huanghua Depression, China - Jinning Zhang; Guomeng Han; Lixin Fu; Hongjun Li; Yuan Neng; Xiao Ma (Arabian Journal of Geosciences, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

Infant exposure to parabens, triclosan, and triclocarban via breastfeeding and formula supplementing in southern China - Duo Zhang; Jinqiu Xiao; Qinru Xiao; Yining Chen; Xiangyu Li; Quanzhi Zheng; Jiaojiao Ma; Jiayi Xu; Jinfeng Fu; Junchun Shen; Lehan Xiao; Shaoyou Lu (Science of The Total Environment, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Modelling and analysis of unsafe acts in coal mine gas explosion accidents based on network theory - Wang Yuxin; Fu Gui; Lyu Qian; Li Xiao; Chen Yiran; Wu Yali; Xie Xuecai (Process Safety and Environmental Protection, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

A multi-agent system based coordinated multi-objective optimal load scheduling strategy using marginal emission factors for building cluster demand response - Hanbei Zhang; Fu Xiao; Chong Zhang; Rongling Li (Energy and Buildings, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Elevational distribution patterns and drivers of soil microbial diversity in the Sygera Mountains, southeastern Tibet, China - Fangwei Fu; Jiangrong Li; Shuaifeng Li; Wensheng Chen; Huihui Ding; Siying Xiao; Yueyao Li (CATENA, 2023)

Experimental and Numerical Investigations on Rock Breaking of TBM Disc Cutter Based on a Novel Platform with Rotational Cutting - Long-Chuan Deng; Fu-Bing Zhang; Xiao-Zhao Li; Chi Zhang; Yu-Kun Ji; Yun Wu (Rock Mechanics and Rock Engineering, 2023)

Multi-source Data-driven Identification of Urban Functional Areas: A Case of Shenyang, China - Bing Xue; Xiao Xiao; Jingzhong Li; Bingyu Zhao; Bo Fu (Chinese Geographical Science, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

UHPLC-QTOF-MS-based untargeted metabolomics and mineral element analysis insight into the geographical differences of Chrysanthemum morifolium Ramat cv. “Hangbaiju” from different origins - Wanjun Long; Xiuyun Bai; Siyu Wang; Hengye Chen; Xiao-Li Yin; Hui-Wen Gu; Jian Yang; Haiyan Fu (Food Research International, 2023)

Novel ionic complex with flame retardancy and ultrastrong toughening effect on epoxy resin - Gaobo Lou; Qingqing Rao; Qing Li; Zhicheng Bai; Xingwei He; Youhua Xiao; Jinfeng Dai; Shenyuan Fu; Shengxiang Yang (Chemical Engineering Journal, 2023)

Atomic doping modulates the electronic structure of porous cobalt phosphide nanosheets as efficient hydrogen generation electrocatalysts in wide pH range - Yonglong Wang; Bin Li; Weiping Xiao; Xinping Wang; Yunlei Fu; Zhenjiang Li; Guangrui Xu; Jianping Lai; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2023)

Streptomyces Spinosirectus sp. nov., Isolated From the Medicinal Plant Xanthium Sibiricum - Yin-Feng Wang; Si-Ren Hu; Li Fu; Yan Xiao; Xin-Ke Tang; Jian Gao (Current Microbiology, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Strong lateral heterogeneities of upper mantle shear-wave structures beneath the central and eastern Tien Shan - Qingya Tang; Weijia Sun; Songjian Ao; Li-Yun Fu; Wenjiao Xiao (International Journal of Earth Sciences, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Iron redistribution induces oxidative burst and resistance in maize against Curvularia lunata - Dandan Fu; Jiayang Li; Xue Yang; Wenling Li; Zengran Zhou; Shuqin Xiao; Chunsheng Xue (Planta, 2022)

Shaking table test and numerical analysis of single-layer reticulated domes with or without three-dimensional isolation bearing - Gui-Bo Nie; Dong-fang Li; Xu-dong Zhi; Fu-yang Wang; Chen-xiao Zhang (Bulletin of Earthquake Engineering, 2022)

Potential millennial‐scale avian declines by humans in southern China - Feng Dong; Qiang Zhang; Yi‐Lin Chen; Fu‐Min Lei; Shou‐Hsien Li; Fei Wu; Xiao‐Jun Yang (Global Change Biology, 2022)
Mounting observational records demonstrate human‐caused faunal decline in recent decades, while accumulating archaeological evidence suggests an early biodiversity impact of human activities during the Holocene. A fundamental question arises concerning whether modern wildlife population declines began during early human disturbance. Here, we performed a population genomic analysis of six common forest birds in East Asia to address this question. For five of them, demographic history inference based on 25–33 genomes of each species revealed dramatic population declines by 4‐ to 48‐fold over millennia (e.g. 2000–5000 thousand years ago). Nevertheless, summary statistics detected nonsignificant correlations between these population size trajectories and Holocene temperature variations, and ecological niche models explicitly predicted extensive range persistence during the Holocene, implying limited demographic consequence of Holocene climate change. Further analyses suggest high negative correlations between the reconstructed population declines and human disturbance intensities and indicate a potential driver of human activities. These findings provide a deep‐time and large‐scale insight into the recently recognized avifaunal decline and support an early origin hypothesis of human effects on biodiversity. Overall, our study sheds light on the current biodiversity crisis in the context of long‐term human–environment interactions and offers a multi‐evidential framework for quantitatively assessing the ecological consequences of human disturbance.

Sedimentary tectonic pattern of Wufeng and Longmaxi Formations in the northern margin of Sichuan Basin, South China - Bin Xiao; Li Xiong; Zhonghai Zhao; Xiang Fu (International Geology Review, 2022)

Role of host plants in the suitability and dispersal of an omnivorous predator Arma chinensis Fallou (Hemiptera: Pentatomidae: Asopinae) in a biological control context - Ming-Zhen Pan; Zhi-Xiao Fu; Yu-Yan Li; Hong-Yin Chen; Li-Sheng Zhang; Tong-Xian Liu (Journal of Plant Diseases and Protection, 2022)

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Dioxin emission and distribution from cement kiln co-processing of hazardous solid waste - Wen-Wen Ye; Peng-Tao Cai; Ming-Xiu Zhan; Wen-Tao Jiao; Xu-Xu; Jian-Ying Fu; Tong Chen; Xiao-Dong Li (Environmental Science and Pollution Research, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

lncRNA BDNF-AS Attenuates Propofol-Induced Apoptosis in HT22 Cells by Modulating the BDNF/TrkB Pathway - Yu-Hai Xu; Yuan Luo; Jiang-Bei Cao; Yan-Hong Liu; Yu-Xiang Song; Xiao-Ying Zhang; Qiang Fu; Wei-Dong Mi; Hao Li (Molecular Neurobiology, 2022)
Propofol is widely used as an intravenous anesthetic in clinical practice. Previous studies have indicated that propofol induces apoptosis in neurons. Brain-derived neurotrophic factor (BDNF), a neurotrophic factor, is associated with neuronal apoptosis. BDNF-AS, a relatively conserved long non-coding RNA, can reverse the transcription of BDNF. This study aimed to investigate the involvement of BDNF-AS in propofol-induced apoptosis in HT22 cells. HT22 cells were treated with various concentrations of propofol at different time points. BDNF-AS was silenced using BDNF-AS-targeting siRNA. TrkB was antagonized by the TrkB inhibitor, ANA-12. Flow cytometry, quantitative reverse-transcription PCR, and western blotting were performed to analyze apoptosis and the expression of genes and proteins, respectively. In propofol-treated HT22 cells, BDNF-AS was upregulated, and BDNF was downregulated in a time- and dose-dependent manner. BDNF-AS downregulation mediated by siRNA mitigated apoptosis, upregulated the expression of Bcl-2, and downregulated the expression of Bax and caspase-3, 7, and 9. ANA-12 downregulated the expression of Bcl-2, upregulated the expression of Bax and caspase-3, 7, and 9, and increased apoptosis. Our study implied that inhibition of BDNF-AS can decrease propofol-induced apoptosis by activating the BDNF/TrkB pathway. Thus, the BDNF-AS-BDNF/TrkB signaling pathway may be a valuable target for treating propofol-induced neurotoxicity.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

Transcriptome Analysis of Sophora davidii Leaves in Response to Low-Phosphorus Stress - Xin Zhao; Li-Juan Huang; Li-Li Zhao; Pu-Chang Wang; Xiao-Fu Sun (Journal of Plant Growth Regulation, 2022)

Assessing the impacts of natural disasters on rice production in Jiangxi, China - Xiao Fu; Guannan Zhao; Weicheng Wu; Bin Xu; Jie Li; Xiaoting Zhou; Xinxin Ke; Yuan Li; Wenjing Li; Cuimin Zhou; Jingheng Jiang; Ming Zhang; et al. (International Journal of Remote Sensing, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Genome-wide identification of HD-ZIP transcription factors in maize and their regulatory roles in promoting drought tolerance - Xiao Qiu; GuoRui Wang; Salah Fatouh Abou-Elwafa; Jiaxu Fu; Zhixue Liu; PengYu Zhang; Xiaowen Xie; Lixia Ku; Ying Ma; XiaoKang Guan; Li Wei (Physiology and Molecular Biology of Plants, 2022)

Differential expression of long non-coding RNAs in the hippocampus of mice exposed to PM2.5 in Dalian, China - Jie Li; Longying Zhang; Jiaqi Wang; Ruxue Jia; Xiao Zhang; Xiaojing Li; Ying Fu; Laiyu Song (Environmental Science and Pollution Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Chemical composition and anti-hepatoma effect of Annona squamosa L. pericarp oil - Ya-Yun Chen; Fu-Qiang Li; Xiao-Li Zhu; Jian-Wei Chen; Xiang Li (Natural Product Research, 2022)

Clinical characteristics of 967 children with pertussis: a single-center analysis over an 8-year period in Beijing, China - Limin Kang; Xiaodai Cui; Jin Fu; Wenpeng Wang; Li Li; Tiegeng Li; Xiaoying Wang; Fei Xiao; Huixue Jia; Rong Mi; Xinlin Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Ferroptosis inhibitory constituents from the fruits of Cullen corylifolium - Aftab Yaseen; Fan Yang; Xia Zhang; Fu Li; Bin Chen; Ahmed Hassan Ibrahim Faraag; Ming-Kui Wang; Xiao-Fei Shen; Lun Wang (Natural Product Research, 2021)

The sesquiterpenes from the stem and leaf of Clausena lansium with their potential antibacterial activities - Xin-Yuan Liu; Xiao-Xiang Fu; Yu-Yan Li; Zhong-Hua Xiong; Bao-Tong Li; Wen-Wen Peng (Natural Product Research, 2021)

Characterization of the novel hybrid cultivar E25 of Saccharina japonica in the northern farming region of China - Li Su; Ti Feng Shan; Jing Li; Su Qin Gao; Shao Jun Pang; Xiao Fei Leng; Yan Zhang; Ming Fu Zhang; Hong Tao Gao (Journal of Applied Phycology, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Targeting of cancer cell death mechanisms by resveratrol: a review - Xiao Fu; Mu Li; Cuilian Tang; Zezhi Huang; Masoud Najafi (Apoptosis, 2021)

Distinct impaired patterns of intrinsic functional network centrality in patients with early- and late-onset Alzheimer’s disease - Jiong Zhou; Kaicheng Li; Xiao Luo; Qingze Zeng; Yerfan Jiaerken; Shuyue Wang; Xiaopei Xu; Xiaocao Liu; Zheyu Li; Tianyi Zhang; Yanv Fu; Shuai Zhao; et al. (Brain Imaging and Behavior, 2021)

An Investigation of Toxic Metal Levels (Pb, Cd, Cr, As, Hg) in Dried Porphyra and Laminaria Collected from Coastal Cities, China - Yan Chen; Yong-tao Liu; Fu-hua Wang; Dian Wen; Hui Yang; Xiao-li Zhao (Biological Trace Element Research, 2021)

Stability Evaluation of Lyotropic Liquid Crystalline Precursor for the Co-delivery of Chlorhexidine and Silver Nanoparticles - Fangqin Fu; Xin Li; Tengyi Zheng; Xiao Xia; Minqun Du; Zhengwei Huang; Ying Huang; Xin Pan; Chuanbin Wu (AAPS PharmSciTech, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Functional characterization of TNF‐ α in pufferfish ( Takifugu obscurus ) in immune response and apoptosis against Aeromonas hydrophila - Linghe Kong; Kun Qian; Siwei Wu; Bingxi Li; Zheng Guo; Xiaoxue Yin; Yu Huang; Jianmin Ye; Xiao Tu; Shengli Fu (Journal of Fish Diseases, 2021)
Tumour necrosis factor‐ α (TNF‐ α ) is a multifunctional cytokine involved in immune system homeostasis, antimicrobial defence, regulation of apoptosis, cell proliferation and differentiation. Although the pro‐inflammatory property of TNF‐ α has been made new progress, detailed research on host defence against bacterial infection and inducing apoptosis remains to be revealed in early vertebrates. Here, we reported the TNF‐ α homologue (ToTNF‐ α ) from pufferfish ( Takifugu obscurus ). The open reading frame (ORF) of ToTNF‐α was 753 bp, encoding a protein of 250 aa contained the TNF family signature and conserved cysteine residues. The mRNA expression of ToTNF‐α had a wide range of tested tissues, with the highest expression in the skin. After Aeromonas hydrophila infection, the mRNA expression of ToTNF‐α was significantly up‐regulated both in vivo and in vitro experiments. After stimulation by recombinant protein of ToTNF‐ α ((r)ToTNF‐ α ), the relative expressions of endogenous TNF‐α , caspase 8 , caspase 3 , p53 , and Bax inhibitor‐1 in head kidney leucocytes were all notably up‐regulated. These results showed that ToTNF‐ α might induce apoptosis depend on pro‐ and anti‐apoptotic proteins at mRNA level. Moreover, flow cytometry analysis indicated that the (r)ToTNF‐ α can induce apoptosis of head kidney leucocytes. Taken together, these characteristics suggest that ToTNF‐α can participate in immune response against A. hydrophila and induce apoptosis at mRNA and cellular level, which will help to understand the mechanism of apoptosis and immune response in teleost fish.

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Resource status and protection strategies of mangroves in China - Xiu-Mei Fu; Hui-Ying Tang; Yang Liu; Meng-Qi Zhang; Shan-Shan Jiang; Fang Yang; Xiao-Yan Li; Chang-Yun Wang (Journal of Coastal Conservation, 2021)
Mangrove is a typical natural landscape with great ecological, social and economic functions and values, and should be highly valued and protected. However, in the past few decades, mangrove resources have suffered serious damage, and there are also many deficiencies in mangrove protection. Chinese mangroves, as an important part of the global mangroves, are of great research value. In the present study, the status and historical dynamic process of Chinese mangrove resources were investigated and discussed to illustrate the problems of resources from three aspects, including mangrove distribution, area and plant species. Based on field research, literature research and data analysis, it was revealed that Chinese mangroves are distributed in eight provinces and regions along the southeast coast with an area of 35,749.25 hm 2 , 38 species and 40 nature reserves. The protection situation and deficiencies were analyzed from the establishment and management of nature reserves. Based on the resource status and problems, reasonable strategies were proposed to protect and manage mangroves mainly from four aspects, including publicity and education, resources restoration and protection technology, legal system establishment, and comprehensive protection and management.

Response of growth characteristics and endogenous hormones of Sophora davidii to low-phosphorus stress - Xin Zhao; Li-Li Zhao; Li-Juan Huang; Xiao-Fu Sun; Pu-Chang Wang (Acta Physiologiae Plantarum, 2021)

Effects of continuous cucumber cropping on crop quality and soil fungal community - Kaining Sun; Longyun Fu; Yang Song; Liang Yuan; Haoran Zhang; Dan Wen; Ning Yang; Xiao Wang; Yaoquan Yue; Xuhua Li; Kean Wang (Environmental Monitoring and Assessment, 2021)

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

Optimal segmentation scale selection and evaluation of cultivated land objects based on high-resolution remote sensing images with spectral and texture features - Heng Lu; Chao Liu; Naiwen Li; Xiao Fu; Longguo Li (Environmental Science and Pollution Research, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Gut microbiome alterations and its link to corticosteroid resistance in immune thrombocytopenia - Yanan Wang; Fengqi Liu; Gaochao Zhang; Yan Su; Xueyan Sun; Qi Chen; Chencong Wang; Haixia Fu; Yun He; Xiaolu Zhu; Xiao Liu; Meng Lv; et al. (Science China Life Sciences, 2021)

Genome-wide association mapping for resistance to bacterial blight and bacterial leaf streak in rice - Nan Jiang; Jun Fu; Qin Zeng; Yi Liang; Yanlong Shi; Zhouwei Li; Youlun Xiao; Zhizhou He; Yuntian Wu; Yu Long; Kai Wang; Yuanzhu Yang; et al. (Planta, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

Diurnal Variations of Precipitation over the Steep Slopes of the Himalayas Observed by TRMM PR and VIRS - Xiao Pan; Yunfei Fu; Sen Yang; Ying Gong; Deqin Li (Advances in Atmospheric Sciences, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

miR-19a mitigates hypoxia/reoxygenation-induced injury by depressing CCL20 and inactivating MAPK pathway in human embryonic cardiomyocytes - Qiang Fu; Tao-Ran Mo; Xiao-Yang Hu; Yin Fu; Ji Li (Biotechnology Letters, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Distinct Effects of Social Stress on Working Memory in Obsessive-Compulsive Disorder - Qianqian Li; Jun Yan; Jinmin Liao; Xiao Zhang; Lijun Liu; Xiaoyu Fu; Hao Yang Tan; Dai Zhang; Hao Yan (Neuroscience Bulletin, 2021)
Stress might exaggerate the compulsion and impair the working memory of patients with obsessive-compulsive disorder (OCD). This study evaluated the effect of stress on the cognitive neural processing of working memory in OCD and its clinical significance using a “number calculation working memory” task. Thirty-eight patients and 55 gender- and education-matched healthy controls were examined. Stress impaired the performance of the manipulation task in patients. Healthy controls showed less engagement of the medial prefrontal cortex and striatum during the task under stress versus less stress, which was absent in the patients with OCD. The diagnosis × stress interaction effect was significant in the right fusiform, supplementary motor area, precentral cortex and caudate. The failure of suppression of the medial prefrontal cortex and striatum and stress-related hyperactivation in the right fusiform, supplementary motor area, precentral cortex, and caudate might be an OCD-related psychopathological and neural response to stress.

Genetic and clinical determinants of mizoribine pharmacokinetics in renal transplant recipients - Rui Dai; Jingjie Li; Jingjing Wu; Qian Fu; Jiajia Yan; Guoping Zhong; Changxi Wang; Xiao Chen; Pan Chen (European Journal of Clinical Pharmacology, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Melatonin ameliorates spatial memory and motor deficits via preserving the integrity of cortical and hippocampal dendritic spine morphology in mice with neurotrauma - Xiao-Jing Lin; Ruoxu Liu; Chenyi Li; Xueqing Yi; Bo Fu; M. J. Walker; Xiao-Ming Xu; Gang Sun; Cheng-Hsien Lin (Inflammopharmacology, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Whole-Brain Map of Long-Range Monosynaptic Inputs to Different Cell Types in the Amygdala of the Mouse - Jia-Yu Fu; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Meng-Yu Tang; Bin Yu; Xiao-Ming Li (Neuroscience Bulletin, 2020)
The amygdala, which is involved in various behaviors and emotions, is reported to connect with the whole brain. However, the long-range inputs of distinct cell types have not yet been defined. Here, we used a retrograde trans-synaptic rabies virus to generate a whole-brain map of inputs to the main cell types in the mouse amygdala. We identified 37 individual regions that projected to neurons expressing vesicular glutamate transporter 2, 78 regions to parvalbumin-expressing neurons, 104 regions to neurons expressing protein kinase C-δ, and 89 regions to somatostatin-expressing neurons. The amygdala received massive projections from the isocortex and striatum. Several nuclei, such as the caudate-putamen and the CA1 field of the hippocampus, exhibited input preferences to different cell types in the amygdala. Notably, we identified several novel input areas, including the substantia innominata and zona incerta. These findings provide anatomical evidence to help understand the precise connections and diverse functions of the amygdala.

Geochemistry and mineralogy of Late Carboniferous coal (No. 8) from the Jialequan Mine, Xishan Coalfield, Shanxi Province, China: evidences for the geologic controls of trace elements - Xiao Li; Jian Kang; Peipei Wang; Yingjie Liu; Qirui Fu (Arabian Journal of Geosciences, 2020)

Dynamic Change of Shanks Gene mRNA Expression and DNA Methylation in Epileptic Rat Model and Human Patients - Yujiao Fu; Du Liu; Jialing Guo; Hongyu Long; Wenbiao Xiao; Wei Xiao; Li Feng; Zhaohui Luo; Bo Xiao (Molecular Neurobiology, 2020)

Sauchinone: a prospective therapeutic agent-mediated EIF4EBP1 down-regulation suppresses proliferation, invasion and migration of lung adenocarcinoma cells - Sheng-Qian Li; Jing Feng; Ming Yang; Xiao-Peng Ai; Mei He; Fu Liu (Journal of Natural Medicines, 2020)

Combined effects of green manure returning and addition of sewage sludge compost on plant growth and microorganism communities in gold tailings - Yan-Jun Ai; Fu-Ping Li; Hai-Hong Gu; Xiao-Jie Chi; Xue-Tao Yuan; Dong-Yun Han (Environmental Science and Pollution Research, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Antifungal, anti-inflamatory and neuritogenic activity of newly-isolated compounds from Disporopsis aspersa - Fang-Li Gang; Feng Zhu; Chao-Fu Yang; Xiao-Ting Li; Hua Yang; Ming-Xia Sun; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2020)

Science and Prediction of Heavy Rainfall over China: Research Progress since the Reform and Opening-Up of New China - Yali Luo; Jisong Sun; Ying Li; Rudi Xia; Yu Du; Shuai Yang; Yuanchun Zhang; Jing Chen; Kan Dai; Xueshun Shen; Haoming Chen; Feifan Zhou; et al. (Journal of Meteorological Research, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

An enhanced index for evaluating natural joint roughness considering multiple morphological factors affecting the shear behavior - Leibo Song; Quan Jiang; Li-fu Li; Chang Liu; Xiao-pei Liu; Jun Xiong (Bulletin of Engineering Geology and the Environment, 2020)

Shaking table test of seismic responses of anchor cable and lattice beam reinforced slope - Jian-jing Zhang; Jia-yong Niu; Xiao Fu; Li-cong Cao; Qiang Xie (Journal of Mountain Science, 2020)

Exogenous salicylic acid alleviates halosulfuron-methyl toxicity by coordinating the antioxidant system and improving photosynthesis in soybean (Glycine max Merr.) - Yuan-Fu Li; Lu-Lu Huang; Xiao-Liang Liu; Xue-Sheng Li; Hui-Hua Tan (Acta Physiologiae Plantarum, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Growth factor regulatory system: a new system for not truly recognized organisms - Jian Xiao; Zhuofeng Lin; Hua Qin; Zhilong Zheng; Fanghua Gong; Yanlong Liu; Xiaokun Li; Xiaobing Fu (Science China Life Sciences, 2020)

Auxin acts as a downstream signaling molecule involved in hydrogen sulfide-induced chilling tolerance in cucumber - Xiao-Wei Zhang; Feng-Jiao Liu; Jiang Zhai; Fu-De Li; Huan-Gai Bi; Xi-Zhen Ai (Planta, 2020)

Vertical variation in Vibrio community composition in Sansha Yongle Blue Hole and its ability to degrade macromolecules - Bei Li; Jiwen Liu; Shun Zhou; Liang Fu; Peng Yao; Lin Chen; Zuosheng Yang; Xiaolei Wang; Xiao-Hua Zhang (Marine Life Science & Technology, 2020)
With the advantages of wide distribution, fast growth, and broad metabolic spectrum to organic carbon compounds, Vibrio may play an important role in organic carbon cycling. However, the ecological roles of Vibrio in many marine environments have not been explored. Here, the world’s deepest ‘blue hole’, the Sansha Yongle Blue Hole (SYBH) in the South China Sea, which is a geographically semi-enclosed environment featuring unique chemical characters, was investigated. The abundance, diversity and carbon source utilization capability of Vibrio were studied by quantification and high-throughput sequencing of Vibrio specific 16S rRNA genes and cultivation methods. The abundance of Vibrio in water column of the SYBH ranged from 3.78 × 10 4 to 7.35 × 10 6 16S rRNA gene copies L −1 . Free-living Vibrio was more abundant than particle-associated Vibrio (~ 1.20 × 10 6 versus~ 2.68 × 10 5 gene copies L −1 ), indicating that Vibrio prefers a free-living life style. The Vibrio assemblages showed clear vertical stratification and could be divided into three groups: aerobic-transition, middle anaerobic and bottom anaerobic zones. Dissolved oxygen (DO), temperature, pH and salinity were the main environmental factors affecting the abundance and community composition. Cultivated Vibrio demonstrated a degrading capability to various macromolecular substrates, including starch, Tween 20/40/80, DNA, gelatin, alginate, casein, chitin, lecithin, κ-carrageenan, mannan, xylan and hyaluronic acid. This suggests that Vibrio could produce a variety of highly active extracellular enzymes. Our study provides new insights into the distribution pattern and possible role in carbon cycle of Vibrio in the unique environment of a ‘blue hole’.

Adjuvant therapy with Astragalus membranaceus for post-stroke fatigue: a systematic review - Li Xu; Xiao-Yan Xu; Xue-Qin Hou; Fu-Gang Wang; Shan Gao; Han-Ting Zhang (Metabolic Brain Disease, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

CRISPR/Cas9 facilitates genomic editing for large-scale functional studies in pluripotent stem cell cultures - Xiao-Fei Li; Yong-Wei Zhou; Peng-Fei Cai; Wei-Cong Fu; Jin-Hua Wang; Jin-Yang Chen; Qi-Ning Yang (Human Genetics, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

The synergetic effect of pelvic rotation and X-ray offset on radiographic angles of the acetabular cup - Jing-Xin Zhao; Xiu-Yun Su; Zhe Zhao; Ruo-Xiu Xiao; Guo-Fei Sun; Li-Cheng Zhang; Pei-Fu Tang (Medical & Biological Engineering & Computing, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Electron Probe Microanalysis of Monazite and Its Applications to U-Th-Pb Dating of Geological Samples - Wenbin Ning; Junpeng Wang; Deng Xiao; Fenfang Li; Bo Huang; Dong Fu (Journal of Earth Science, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

The orphan nuclear receptor NUR77 promotes trophoblast invasion at early pregnancy through paracrine placental growth factor - Xiao-Cui Li; Xiang-Jie Yin; Wei Hong; Jie Liu; Feng Jin; Bei-Ying Wang; Yu-Mei Wang; Fu-Ju Tian (Journal of Molecular Medicine, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

1,1-Diaryl compounds as important bioactive module in pesticides - Xuelian Liu; Yumei Xiao; Jia-Qi Li; Bin Fu; Zhaohai Qin (Molecular Diversity, 2019)

Transcriptome-based Discovery of AP2/ERF tRanscription Factors and Expression Profiles Under Herbivore Stress Conditions in Bamboo (Bambusa emeiensis) - Yuanqiu Li; Chaobing Luo; Ying Chen; Ximeng Xiao; Chun Fu; Yaojun Yang (Journal of Plant Biology, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Non-coding RNAs and transposable elements in plant genomes: emergence, regulatory mechanisms and roles in plant development and stress responses - Jinna Hou; Dandan Lu; Annaliese S. Mason; Baoquan Li; Meili Xiao; Sufang An; Donghui Fu (Planta, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Glacier extent changes and possible causes in the Hala Lake Basin of Qinghai-Tibet Plateau - Dong-Sheng Li; Bu-Li Cui; Ying Wang; Bei Xiao; Bao-Fu Jiang (Journal of Mountain Science, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Timing and genesis of Cu–(Au) mineralization in the Khetri Copper Belt, northwestern India: constraints from in situ U–Pb ages and Sm–Nd isotopes of monazite-(Ce) - Xiao-Chun Li; Mei-Fu Zhou; A. E. Williams-Jones; Yue-Heng Yang; Jian-Feng Gao (Mineralium Deposita, 2019)

Regulation of flowering time via miR172-mediated APETALA2-like expression in ornamental gloxinia (Sinningia speciosa) - Xiao-yan Li; Fu Guo; Sheng-yun Ma; Mu-yuan Zhu; Wei-huai Pan; Hong-wu Bian (Journal of Zhejiang University-SCIENCE B, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

The IMPDH inhibitors, ribavirin and mycophenolic acid, inhibit peste des petits ruminants virus infection - Qiu-yan Chang; Fu-cheng Guo; Xue-rui Li; Jian-hua Zhou; Xuepeng Cai; Qiuwei Pan; Xiao-xia Ma (Veterinary Research Communications, 2018)

A new polyoxygenated abietane diterpenoid from the rattans of Bauhinia championii (Benth.) Benth - Li-Ping Hua; Yu-Qin Zhang; Miao Ye; Wen Xu; Xiao-Ying Wang; Yan-Hui Fu; Wei Xu (Natural Product Research, 2018)

Tree species mixture inhibits soil organic carbon mineralization accompanied by decreased r-selected bacteria - Xiao Zhang; Shirong Liu; Yongtao Huang; Shenglei Fu; Jingxin Wang; Angang Ming; Xiangzhen Li; Minjie Yao; Huan Li (Plant and Soil, 2018)

Effect of controlled-release fertilizer on N2O emissions and tea yield from a tea field in subtropical central China - Yanzheng Wu; Yong Li; Xiaoqing Fu; Jianlin Shen; Dan Chen; Yi Wang; Xinliang Liu; Runlin Xiao; Wenxue Wei; Jinshui Wu (Environmental Science and Pollution Research, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

An inversion of transient electromagnetic data from a conical source - Hai-Yan Yang; Feng-Ping Li; Shen-En Chen; Jian-Hua Yue; Fu-Sheng Guo; Xiao Chen; Hua Zhang (Applied Geophysics, 2018)

Spatiotemporal analysis of the agricultural drought risk in Heilongjiang Province, China - Wei Pei; Qiang Fu; Dong Liu; Tian-xiao Li; Kun Cheng; Song Cui (Theoretical and Applied Climatology, 2018)

Detoxification of aflatoxins on prospective approach: effect on structural, mechanical, and optical properties under pressures - Yong-Kai Wei; Xiao-Miao Zhao; Meng-Meng Li; Jing-Xin Yu; Selvaraj Gurudeeban; Yan-Fei Hu; Guang-Fu Ji; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Red mud-modified biochar reduces soil arsenic availability and changes bacterial composition - Qi Zou; Wenhui An; Chuan Wu; Waichin Li; Anqin Fu; Ruiyang Xiao; Huikang Chen; Shengguo Xue (Environmental Chemistry Letters, 2018)

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

Seismic responses of the steel-strip reinforced soil retaining wall with full-height rigid facing from shaking table test - Li-cong Cao; Xiao Fu; Zhi-jia Wang; Yong-yi Zhou; Fei-cheng Liu; Jian-jing Zhang (Journal of Mountain Science, 2018)

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

HAP1 Is Required for Endocytosis and Signalling of BDNF and Its Receptors in Neurons - Yoon Lim; Linda Lin-Yan Wu; Si Chen; Ying Sun; Swarna Lekha Vijayaraj; Miao Yang; Larisa Bobrovskaya; Damien Keating; Xiao-Jiang Li; Xin-Fu Zhou (Molecular Neurobiology, 2018)

Uranium-lead dating of hydrothermal zircon and monazite from the Sin Quyen Fe-Cu-REE-Au-(U) deposit, northwestern Vietnam - Xiao-Chun Li; Mei-Fu Zhou; Wei Terry Chen; Xin-Fu Zhao; MyDung Tran (Mineralium Deposita, 2018)

OsGLO4 is involved in the formation of iron plaques on surface of rice roots grown under alternative wetting and drying condition - Xiao-Li Yu; Dao-Ming Wu; You-Qiang Fu; Xu-Jian Yang; František Baluška; Hong Shen (Plant and Soil, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Fine mapping of the Brassica napus Bnsdt1 gene associated with determinate growth habit - Kaixiang Li; Yanmei Yao; Lu Xiao; Zhigang Zhao; Shaomin Guo; Zhong Fu; Dezhi Du (Theoretical and Applied Genetics, 2018)

Physical interactions and mutational analysis of MoYpt7 in Magnaporthe oryzae - Lu-yao Huang; Min Wu; Xiao-yun Yu; Lin Li; Fu-cheng Lin; Xiao-hong Liu (Journal of Zhejiang University-SCIENCE B, 2018)

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection - Tianwen Li; Yongfu Shao; Liyun Fu; Yi Xie; Linwen Zhu; Weiliang Sun; Rui Yu; Bingxiu Xiao; Junming Guo (Journal of Molecular Medicine, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

CXCL10 suppression of hem- and lymph-angiogenesis in inflamed corneas through MMP13 - Nan Gao; Xiaowei Liu; Jiayin Wu; Juan Li; Chen Dong; Xinyi Wu; Xiao Xiao; Fu-Shin X. Yu (Angiogenesis, 2017)

Black-and-white snub-nosed monkey (Rhinopithecus bieti) feeding behavior in a degraded forest fragment: clues to a stressed population - Zhi-Pang Huang; Matthew B. Scott; Yan-Peng Li; Guo-Peng Ren; Zuo-Fu Xiang; Liang-Wei Cui; Wen Xiao (Primates, 2017)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Complete genome sequence of Halomonas ventosae virulent halovirus QHHSV-1 - Chaoqun Fu; Qin Zhao; Zhiying Li; Yongxia Wang; Shiying Zhang; Yonghong Lai; Wei Xiao; Xiaolong Cui (Archives of Virology, 2017)

Development of Albumin Coupled, Cholesterol Stabilized, Lipid Nanoemulsion of Methotrexate, and TNF-α Inhibitor for Improved In Vivo Efficacy Against Rheumatoid Arthritis - Xiao-yan Li; Hui Li; Yan Zhang; Shan Gao; Chun-ping Dong; Gui-fu Wu (AAPS PharmSciTech, 2017)

Mutant p53 promotes cell spreading and migration via ARHGAP44 - Jinjin Xu; Jian Jiao; Wei Xu; Lei Ji; Dongjie Jiang; Shaofang Xie; Syeda Kubra; Xiaotao Li; Junjiang Fu; Jianru Xiao; Bianhong Zhang (Science China Life Sciences, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Perfluoroalkyl substances with isomer analysis in umbilical cord serum in China - Ya-Zhi Zhang; Xiao-Wen Zeng; Zhengmin Qian; Michael G. Vaughn; Sarah Dee Geiger; Li-Wen Hu; Long Lu; Chuanxi Fu; Guang-Hui Dong (Environmental Science and Pollution Research, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Cultivated land information extraction in UAV imagery based on deep convolutional neural network and transfer learning - Heng Lu; Xiao Fu; Chao Liu; Long-guo Li; Yu-xin He; Nai-wen Li (Journal of Mountain Science, 2017)

Measurement and modeling of nitrous and nitric oxide emissions from a tea field in subtropical central China - Dan Chen; Yong Li; Cong Wang; Xiaoqing Fu; Xinliang Liu; Jianlin Shen; Yi Wang; Runlin Xiao; De Li Liu; Jinshui Wu (Nutrient Cycling in Agroecosystems, 2017)

Evaluation of the land carrying capacity of major grain-producing areas and the identification of risk factors - Kun Cheng; Qiang Fu; Song Cui; Tian-xiao Li; Wei Pei; Dong Liu; Jun Meng (Natural Hazards, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Early Cretaceous porphyry copper mineralization in Northeast China: the Changfagou example - Yong Zhang; Shu–Wen Xing; Chao Li; Shi–Fu Liang; Zheng–Tao Yu; Xiao–Hui Du; Yan Wang; Zeng–Jie Zhang; Yu–Bo Ma (International Geology Review, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Haplotype of platelet receptor P2RY12 gene is associated with residual clopidogrel on-treatment platelet reactivity - Xiao-yan Nie; Jun-lei Li; Yong Zhang; Yang Xu; Xue-li Yang; Yu Fu; Guang-kai Liang; Yun Lu; Jian Liu; Lu-wen Shi (Journal of Zhejiang University-SCIENCE B, 2017)

Regional efforts to mitigate climate change in China: a multi-criteria assessment approach - Zhi-Fu Mi; Yi-Ming Wei; Chen-Qi He; Hua-Nan Li; Xiao-Chen Yuan; Hua Liao (Mitigation and Adaptation Strategies for Global Change, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Dynamic failure mode and energy-based identification method for a counter-bedding rock slope with weak intercalated layers - Gang Fan; Jian-jing Zhang; Xiao Fu; Li-rong Zhou (Journal of Mountain Science, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Effects of bypass system on PCDD/F emission and chlorine circulation in cement kilns - Ming-Xiu Zhan; Jianying Fu; Tong Chen; Yeqing Li; Jiang Zhang; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Small RNA changes in synthetic Brassica napus - Ying Fu; Meili Xiao; Huasheng Yu; Annaliese S. Mason; Jiaming Yin; Jiana Li; Dongqing Zhang; Donghui Fu (Planta, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Directed differentiation of human embryonic stem cells into keratinocyte progenitors in vitro: an attempt with promise of clinical use - Hanqing Li; Haiwen Zhou; Xin Fu; Ran Xiao (In Vitro Cellular & Developmental Biology - Animal, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Antiviral activity of recombinant porcine surfactant protein A against porcine reproductive and respiratory syndrome virus in vitro - Lan Li; Qisheng Zheng; Yuanpeng Zhang; Pengcheng Li; Yanfeng Fu; Jibo Hou; Xilong Xiao (Archives of Virology, 2016)

Genome-wide identification of WRKY family genes in peach and analysis of WRKY expression during bud dormancy - Min Chen; Qiuping Tan; Mingyue Sun; Dongmei Li; Xiling Fu; Xiude Chen; Wei Xiao; Ling Li; Dongsheng Gao (Molecular Genetics and Genomics, 2016)

Assessing agricultural drought vulnerability in the Sanjiang Plain based on an improved projection pursuit model - Wei Pei; Qiang Fu; Dong Liu; Tian-xiao Li; Kun Cheng (Natural Hazards, 2016)

Plasma Homocysteine Levels Predict the Risk of Acute Cerebral Infarction in Patients with Carotid Artery Lesions - Wei Wu; Yi Guan; Kan Xu; Xi-Jia Fu; Xiao-Feng Lei; Li-Jian Lei; Zhi-Qing Zhang; Yan Cheng; Yun-Qian Li (Molecular Neurobiology, 2016)

DNA Methylation Profiling Reveals Correlation of Differential Methylation Patterns with Gene Expression in Human Epilepsy - Liang Wang; Xinwei Fu; Xi Peng; Zheng Xiao; Zhonggui Li; Guojun Chen; Xuefeng Wang (Journal of Molecular Neuroscience, 2016)

OsBAK1 is involved in rice resistance to Xanthomonas oryzae pv. oryzae PXO99 - Hualan Liao; Xiaorong Xiao; Xiuqiong Li; Yan Chen; Xiumei Fu; Daozhe Lin; Xiaolei Niu; Yinhua Chen; Chaozu He (Plant Biotechnology Reports, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Overexpression of the Gibberellin 2-Oxidase Gene from Camellia lipoensis Induces Dwarfism and Smaller Flowers in Nicotiana tabacum - Zheng Xiao; Ruipeng Fu; Jiyuan Li; Zhengqi Fan; Hengfu Yin (Plant Molecular Biology Reporter, 2016)

Re–Os and U–Pb geochronology of the Laochang Pb–Zn–Ag and concealed porphyry Mo mineralization along the Changning–Menglian suture, SW China: implications for ore genesis and porphyry Cu–Mo exploration - Xiao-Dong Deng; Jian-Wei Li; Xin-Fu Zhao; Hong-Qiang Wang; Liang Qi (Mineralium Deposita, 2016)

Antinociceptive effects induced by intra-lateral habenula complex injection of the galanin receptor 1 agonist M617 in rats - Li-Bo Fu; Ying Wang; Xiao-Xiao Sun; Xiao-Xia Liu; Ying Wang; Wen Zhuang (Experimental Brain Research, 2016)

Strategy to Suppress Oxidative Damage-Induced Neurotoxicity in PC12 Cells by Curcumin: the Role of ROS-Mediated DNA Damage and the MAPK and AKT Pathways - Xiao-yan Fu; Ming-feng Yang; Ming-zhi Cao; Da-wei Li; Xiao-yi Yang; Jing-yi Sun; Zong-yong Zhang; Lei-lei Mao; Shuai Zhang; Feng-ze Wang; Feng Zhang; Cun-dong Fan; et al. (Molecular Neurobiology, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

Automated rapid iterative negative geotaxis assay and its use in a genetic screen for modifiers of Aβ42-induced locomotor decline in Drosophila - Haiyan Liu; Meng Han; Qingyi Li; Xiao Zhang; Wen-An Wang; Fu-De Huang (Neuroscience Bulletin, 2015)

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells - Yan-Jie Lu; Zhi-Jun Geng; Xiao-Yan Sun; Yu-Hong Li; Xiao-Bing Fu; Xiang-Yang Zhao; Bo Wei (Molecular and Cellular Biochemistry, 2015)

In situ Sr isotope analysis of apatite by LA-MC-ICPMS: constraints on the evolution of ore fluids of the Yinachang Fe-Cu-REE deposit, Southwest China - Xin-Fu Zhao; Mei-Fu Zhou; Jian-Feng Gao; Xiao-Chun Li; Jian-Wei Li (Mineralium Deposita, 2015)

High abundances of dicarboxylic acids, oxocarboxylic acids, and α-dicarbonyls in fine aerosols (PM2.5) in Chengdu, China during wintertime haze pollution - Xiao-dong Li; Zhou Yang; Pingqing Fu; Jing Yu; Yun-chao Lang; Di Liu; Kaori Ono; Kimitaka Kawamura (Environmental Science and Pollution Research, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Transport of short-chain perfluoroalkyl acids from concentrated fluoropolymer facilities to the Daling River estuary, China - Pei Wang; Yonglong Lu; Tieyu Wang; Zhaoyun Zhu; Qifeng Li; Yueqing Zhang; Yaning Fu; Yang Xiao; John P. Giesy (Environmental Science and Pollution Research, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Generation of outbred Ace2 knockout mice by RNA transfection of TALENs displaying colitis reminiscent pathophysiology and inflammation - Chuxin Liu; Liping Xiao; Feida Li; Huanhuan Zhang; Qin Li; Huan Liu; Shujin Fu; Chao Li; Xingju Zhang; Jun Wang; Nicklas H. Staunstrup; Yong Li; et al. (Transgenic Research, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Challenges and adaptations of farming to climate change in the North China Plain - Hai-Lin Zhang; Xin Zhao; Xiao-Gang Yin; Sheng-Li Liu; Jian-Fu Xue; Meng Wang; Chao Pu; Rattan Lal; Fu Chen (Climatic Change, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

What is crop heterosis: new insights into an old topic - Donghui Fu; Meili Xiao; Alice Hayward; Guanjie Jiang; Longrong Zhu; Qinghong Zhou; Jiqiang Li; Min Zhang (Journal of Applied Genetics, 2015)

Mapping of quantitative trait loci for cold tolerance at the early seedling stage in landrace rice Xiang 743 - Wenqiang Liu; Tingting Lu; Yongchao Li; Xiaowu Pan; Yonghong Duan; Jun Min; Xiqin Fu; Xinnian Sheng; Junzhi Xiao; Sanxiong Liu; Jiang Tan; Yi Yao; et al. (Euphytica, 2015)

Advances in cloud physics and weather modification in China - Xueliang Guo; Danhong Fu; Xingyu Li; Zhaoxia Hu; Henchi Lei; Hui Xiao; Yanchao Hong (Advances in Atmospheric Sciences, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

Genetic tools for the piezophilic hyperthermophilic archaeon Pyrococcus yayanosii - Xuegong Li; Ling Fu; Zhen Li; Xiaopan Ma; Xiang Xiao; Jun Xu (Extremophiles, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

Construction of a lentiviral T/A vector for direct analysis of PCR-amplified promoters - Fu-xian Yu; Zhi-wei Zhu; Xiao-yu Chen; Jing Huang; Tuan-yuan Shi; Jun-xing Li; Jian-zhi Pan (Molecular Biology Reports, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Detection of Nosema bombycis by FTA Cards and Loop-Mediated Isothermal Amplification (LAMP) - Wei Yan; Zhongyuan Shen; Xudong Tang; Li Xu; Qianlong Li; Yajie Yue; Shengyan Xiao; Xuliang Fu (Current Microbiology, 2014)

Acutissimanide, a new lignan with antioxidant activity isolated from the bark of Quercus acutissima Carruth - Xiao-Li Zeng; Guang-Miao Fu; Kai Tian; Jing-Xian Sun; Hua-Bin Xiong; Xiang-Zhong Huang; Zhi-Yong Jiang (Natural Product Research, 2014)

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Isolation and characterization of microsatellite loci in the endangered Amur ratsnake Elaphe schrenckii (Reptilia; Squamata; Colubridae) from China - Xue-yang Xu; Tian-long Fu; Yan-Fu Qu; Xiao-xiao Zheng; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2014)

Phylogenetic assessment of Chaetomium indicum and allied species, with the introduction of three new species and epitypification of C. funicola and C. indicum - Xue-Wei Wang; Xiao-Liang Wang; Fu-Jiang Liu; Xiao-Meng Zhao; Jing Li; Lei Cai (Mycological Progress, 2014)

Landscape pattern changes at a catchment scale: a case study in the upper Jinjing river catchment in subtropical central China from 1933 to 2005 - Xinliang Liu; Yong Li; Jianlin Shen; Xiaoqing Fu; Runlin Xiao; Jinshui Wu (Landscape and Ecological Engineering, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Horizontal gene transfer in plants - Caihua Gao; Xiaodong Ren; Annaliese S. Mason; Honglei Liu; Meili Xiao; Jiana Li; Donghui Fu (Functional & Integrative Genomics, 2014)

Purification and characterization of a thermostable aliphatic amidase from the hyperthermophilic archaeon Pyrococcus yayanosii CH1 - Ling Fu; Xuegong Li; Xiang Xiao; Jun Xu (Extremophiles, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

A Novel Co-immunoprecipitation Protocol Based on Protoplast Transient Gene Expression for Studying Protein–protein Interactions in Rice - Jia Wei Yang; Jia Xin Fu; Jing Li; Xiao Ling Cheng; Feng Li; Jing Fang Dong; Zhen Lan Liu; Chu Xiong Zhuang (Plant Molecular Biology Reporter, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Extensive tRNA Gene Changes in Synthetic Brassica napus - Lijuan Wei; Zeshan An; Annaliese S. Mason; Meili Xiao; Ying Guo; Jiaming Yin; Jiana Li; Donghui Fu (Journal of Molecular Evolution, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Breed-linked polymorphisms of porcine toll-like receptor 2 (TLR2) and TLR4 and the primary investigation on their relationship with prevention against Mycoplasma pneumoniae and bacterial LPS challenge - Xiaomin Fang; Xiao Liu; Cui Meng; Yanfeng Fu; Xuemin Wang; Bixia Li; Feng Tu; Fang Zhao; Shouwen Ren (Immunogenetics, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Targeted editing of goat genome with modular-assembly zinc finger nucleases based on activity prediction by computational molecular modeling - Kai Xiong; Shanshan Li; Hongxiao Zhang; Ye Cui; Debing Yu; Yan Li; Wenxing Sun; Yingying Fu; Yun Teng; Zhi Liu; Xiaolong Zhou; Peng Xiao; et al. (Molecular Biology Reports, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Effects of zinc-substituted nano-hydroxyapatite coatings on bone integration with implant surfaces - Shi-fang Zhao; Wen-jing Dong; Qiao-hong Jiang; Fu-ming He; Xiao-xiang Wang; Guo-li Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Characterization and evolutionary analysis of Brassica species-diverged sequences containing simple repeat units - Lijuan Wei; Meili Xiao; Annaliese S. Mason; Bi Ma; Kun Lu; Jiana Li; Link Katrin; Donghui Fu (Genes & Genomics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Efficacy of endosulfan and fipronil and joint toxic action of endosulfan mixtures against Leptinotarsa decemlineata (Say) - Xiao-qin Shi; Man-Hui Xiong; Wei-Hua Jiang; Zhi-Tian Wang; Wen-Chao Guo; Zhen-Han Xia; Wen-Jun Fu; Guo-Qing Li (Journal of Pest Science, 2012)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Roseibacterium beibuensis sp. nov., a Novel Member of Roseobacter Clade Isolated from Beibu Gulf in the South China Sea - Yujiao Mao; Jingjing Wei; Qiang Zheng; Na Xiao; Qipei Li; Yingnan Fu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

RETRACTED ARTICLE: A 2-D DIGE analysis of simulated acid rain-responsive proteins in Pinus massoniana needles - Ting-Wu Liu; Wen-Jun Hu; Xiao-Qin Wang; Li Niu; Bin Fu; Fei-Hua Wu; Zhen-Ming Pei; Hai-Lei Zheng (Trees, 2012)

Erratum to: Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Characterization of transcriptional activation and inserted-into-gene preference of various transposable elements in the Brassica species - Caihua Gao; Meili Xiao; Lingyan Jiang; Jiana Li; Jiaming Yin; Xiaodong Ren; Wei Qian; Ortegón Oscar; Donghui Fu; Zhanglin Tang (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Phytotoxicity of Thiocyanate to Rice Seedlings - Xiao-Zhang Yu; Fu-Zhong Zhang; Fan Li (Bulletin of Environmental Contamination and Toxicology, 2012)

Protective effects of 7-difluoromethyl-5,4′-dimethoxygenistein against human aorta endothelial injury caused by lysophosphatidyl choline - Fei Liu; Jian-Guo Cao; Cheng Li; Jin-Seng Tan; Xiao-Hua Fu (Molecular and Cellular Biochemistry, 2012)

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

Integrin-mediated signaling contributes to gadolinium-containing-particle-promoted cell survival and G1 to S phase cell cycle transition by enhancing focal adhesion formation - Jin-Xia Li; Li-Juan Fu; Xiao-Gai Yang; Kui Wang (JBIC Journal of Biological Inorganic Chemistry, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

Variational retrieval of leaf area index from MODIS time series data: examples from the Heihe river basin, north-west China - Zhiqiang Xiao; Jindi Wang; Shunlin Liang; Hongmin Zhou; Xijia Li; Liqiang Zhang; Ziti Jiao; Yan Liu; Zhuo Fu (International Journal of Remote Sensing, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Noradrenaline regulates substance P release from rat dorsal root ganglion neurons in vitro - Yan-Jie Wang; Xing-Fu Li; Feng Ding; Qiang Shu; Li-Jun Song; Xiao Yu; Hua-Xiang Liu (Neuroscience Bulletin, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Molecular authentication of geo-authentic Scrophularia ningpoensis - Chuan Chen; Li-na Duan; Xiao-long Zhou; Bing-long Chen; Cheng-xin Fu (Journal of Zhejiang University-SCIENCE B, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

A novel human derived cell-penetrating peptide in drug delivery - Jian Zhao; Peng Gao; Wei Xiao; Li-Qiang Fan; Fu-Jun Wang; Su-Xia Li; Jian-Wen Liu (Molecular Biology Reports, 2011)

Overyielding and interspecific interactions mediated by nitrogen fertilization in strip intercropping of maize with faba bean, wheat and barley - Qiu-Zhu Li; Jian-Hao Sun; Xiao-Jing Wei; Peter Christie; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Association between NMDA receptor subunit 2b gene polymorphism and Alzheimer’s disease in Chinese Han population in Shanghai - Chao Chen; Xia Li; Tao Wang; Hai-Hong Wang; Yi Fu; Lei Zhang; Shi-Fu Xiao (Neuroscience Bulletin, 2010)

Targeted antitumor effect induced by hTERT promoter mediated ODC antisense adenovirus - Wei Wang; Bin Jin; Wei Li; Chun-Xiao Xu; Fu-Ai Cui; Bin Liu; Yun-Fei Yan; Xian-Xi Liu; Xiu-Li Wang (Molecular Biology Reports, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Population variation of invasive Spartina alterniflora can differentiate bacterial diversity in its rhizosphere - Ming Nie; Le Xuan Gao; Jun Hong Yan; Xiao Hua Fu; Ming Xiao; Ji Yang; Bo Li (Plant Ecology, 2010)

Spatial Characteristics and Major Sources of Polycyclic Aromatic Hydrocarbons from Soil and Respirable Particulate Matter in a Mega-City, China - Shan Fu; Zhong-Zhi Yang; Ke Li; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Prostasin inhibits cell invasion in human choriocarcinomal JEG-3 cells - Xiao-jie Ma; Ya-yuan Fu; Yu-xia Li; Li-mei Chen; Karl Chai; Yan-ling Wang (Histochemistry and Cell Biology, 2009)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Tunicamycin suppresses cisplatin-induced HepG2 cell apoptosis via enhancing p53 protein nuclear export - Li-Juan Zhang; Zai-Quan Li; Ye-Peng Yang; Xiao-Wen Li; Jia-Fu Ji (Molecular and Cellular Biochemistry, 2009)

Gadolinium promoted proliferation and enhanced survival in human cervical carcinoma cells - Ying Zhang; Li-Juan Fu; Jin-Xia Li; Xiao-Gai Yang; Xiao-Da Yang; Kui Wang (BioMetals, 2009)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Molecular cloning and characterization of a novel transcript variant of Mtsarg1 gene - Li Li; Gang Liu; Jun-Jiang Fu; Lu-Yun Li; Xiao-Jun Tan; Sheng Yang; Guang-Xiu Lu (Molecular Biology Reports, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Determination of soluble solid content and acidity of loquats based on FT-NIR spectroscopy - Xia-ping Fu; Jian-ping Li; Ying Zhou; Yi-bin Ying; Li-juan Xie; Xiao-ying Niu; Zhan-ke Yan; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Gadolinium-promoted cell cycle progression with enhanced S-phase entry via activation of both ERK and PI3K signaling pathways in NIH 3T3 cells - Li-Juan Fu; Jin-Xia Li; Xiao-Gai Yang; Kui Wang (JBIC Journal of Biological Inorganic Chemistry, 2009)

Molecular genetic structure and evolution in native and colonized populations of the Chinese mitten crab, Eriocheir sinensis - Chenghui Wang; Sifa Li; Cuizhang Fu; Xiaoling Gong; Len Huang; Xiao Song; Yan Zhao (Biological Invasions, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Increased pathogenesis and inflammation of airways from respiratory syncytial virus infection in T cell deficient nude mice - Juan Zhou; Xi-Qiang Yang; Zhou Fu; Xiao-Dong Zhao; Li-Ping Jiang; Li-Jia Wang; Yu-Xia Cui (Medical Microbiology and Immunology, 2008)

One-step preparation of antibody and oligonucleotide dual-labeled gold nanoparticle bio-probes and their properties - Xiao-li Kong; Fei-yan Qiao; Hui Qi; Fu-rong Li (Biotechnology Letters, 2008)

Extensive population expansion of Pedicularis longiflora (Orobanchaceae) on the Qinghai‐Tibetan Plateau and its correlation with the Quaternary climate change - FU‐SHENG YANG; YU‐FEI LI; XIN DING; XIAO‐QUAN WANG (Molecular Ecology, 2008)
The Qinghai‐Tibetan Plateau (QTP) is thought to be more strongly affected by the Quaternary glaciations than most other regions of the same latitude. It would be of great interest to investigate the population genetic structure of organisms distributed on the platform and its correlation with the Quaternary climatic oscillations. Here we used the chloroplast (cp)DNA trn T‐ trn F sequence to study genetic variation and phylogeography of Pedicularis longiflora , an alpine herb with extensive distribution on the QTP. Based on a range‐wide sampling comprising 41 populations and 910 individuals, we detected 30 cpDNA haplotypes that were divided into five clades by phylogenetic and network analyses and a strong phylogeographical structure. All haplotypes but one in the three basal clades occur exclusively in the southeast QTP, whereas haplotypes in the young clade V occupy almost the whole species range. In particular, the young haplotype H18 occurs in 420 individuals, even at a frequency of 100% in some QTP platform populations and the Altai population. The haplotype distribution pattern, together with molecular clock estimation and mismatch distribution analysis, suggests that the southeast QTP was either a refuge for P . longiflora during the Quaternary climatic change or is the place of origin of the species. The present wide distribution of the species on the QTP platform has resulted from recent population expansions which could be dated back to 120 000–17 000 years ago, a period mostly before the last glacial maximum. The possible relationships among geographic genetic structure, climatic change and species diversification in Pedicularis are also discussed.

Initial analysis of the mechanism of the Wenchuan Earthquake (Southwest China), 12 May 2008 - Wu Faquan; Fu Bihong; Li Xiao; Liu Jianyou (Bulletin of Engineering Geology and the Environment, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Magnaporthe oryzae MTP1 gene encodes a type III transmembrane protein involved in conidiation and conidial germination - Qin Lu; Jian-ping Lu; Xiao-dong Li; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Research on the Components of Dust Fall in Hohhot in Comparison with Surface Soil Components in Different Lands of Inner Mongolia Plateau - Chun-xing Hai; Chun-shin Yuan; Guang-tong Liu; Xiao-jia Li; Fu Zhang; Xiu-jiang Zhang (Water, Air, & Soil Pollution, 2008)

The concentrations, distribution and sources of PAHs in agricultural soils and vegetables from Shunde, Guangdong, China - Yong Tao Li; Fang Bai Li; Jun Jian Chen; Guo Yi Yang; Hong Fu Wan; Tian Bin Zhang; Xiao Duo Zeng; Jian Ming Liu (Environmental Monitoring and Assessment, 2008)

Origin of the Tongshankou porphyry–skarn Cu–Mo deposit, eastern Yangtze craton, Eastern China: geochronological, geochemical, and Sr–Nd–Hf isotopic constraints - Jian-Wei Li; Xin-Fu Zhao; Mei-Fu Zhou; Paulo Vasconcelos; Chang-Qian Ma; Xiao-Dong Deng; Zorano Sérgio de Souza; Yong-Xin Zhao; Gang Wu (Mineralium Deposita, 2008)

Molecular and functional comparisons of the vacuolar Na+/H+ exchangers originated from glycophytic and halophytic species - Jin-yao Li; Xiao-wei He; Li Xu; Jie Zhou; Ping Wu; Hui-xia Shou; Fu-chun Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Isolation of a human gallbladder cancer cell clone with high invasive phenotype in vitro and metastatic potential in orthotopic model and inhibition of its invasiveness by heparanase antisense oligodeoxynucleotides - Xin-Zhong Chang; Zhan-Min Wang; Jin-Ming Yu; Fu-Guo Tian; Wei Jin; Yi Zhang; Jie Yu; Lian-Fang Li; Xiao-Feng Liu; Zhi-Wei Li; Zhi-Min Shao (Clinical & Experimental Metastasis, 2007)

Expression of SWAP-70 in the uterus and feto-maternal interface during embryonic implantation and pregnancy in the rhesus monkey (Macaca mulatta) - Jing Liu; Ya-Yuan Fu; Xiao-Yang Sun; Fei-Xue Li; Yu-Xia Li; Yan-Ling Wang (Histochemistry and Cell Biology, 2006)

Effects of dietary supplementation with Clostridium butyricum on the growth performance and humoral immune response in Miichthys miiuy - Zeng-fu Song; Tian-xing Wu; Li-sheng Cai; Li-jing Zhang; Xiao-dong Zheng (Journal of Zhejiang University-SCIENCE B, 2006)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)

Treatment of spinal cord injury with co-grafts of genetically modified schwann cells and fetal spinal cord cell suspension in the rat - Shi -Qing Feng; Xiao -Hong Kong; Shi -Fu Guo; Pei Wang; Li Li; Jin -Hua Zhong; Xin -Fu Zhou (Neurotoxicity Research, 2005)

Absence of Archean basement in the South Kunlun Block: Nd‐Sr‐O isotopic evidence from granitoids - Chao Yuan; Min Sun; Mei‐Fu Zhou; Hui Zhou; Wenjiao Xiao; Jiliang Li (Island Arc, 2003)
The West Kunlun mountain range along the northwestern margin of the Tibetan Plateau is crucial in understanding the early tectonic history of the region. It can be divided into the North and South Kunlun Blocks, of which the former is considered to be part of the Tarim Craton, whereas consensus was not reached on the nature and origin of the South Kunlun Block. Samples were collected from the 471 Ma Yirba Pluton, the 405 Ma North Kudi Pluton and the 214 Ma Arkarz Shan Intrusive Complex. These granitoids cover approximately 60% of the Kudi area in the South Kunlun Block. Sr, Nd, and O isotope compositions preclude significant involvement of mantle‐derived magma in the genesis of these granitoids; therefore, they can be used to decipher the nature of lower–mid crust in the area. All samples give Mesoproterozoic Nd model ages (1.1–1.5 Ga) similar to those of the exposed metamorphic complex of this block but significantly different from those of the basement of the North Kunlun Block (2.8 Ga). This indicates that the South Kunlun Block does not have an Archean basement, and, thus, does not support the microcontinent model that suggests the South Kunlun Block was a microcontinent once separated from and later collided back with the North Kunlun Block.

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Addenda - Xiao-feng Fu; Zhe Li (Journal of Geographical Sciences, 2001)

On coordinated development of oasis and environment in arid area - Fu Xiao-feng; Li Zhe (Journal of Geographical Sciences, 2001)

Oxygen and hydrogen isotope geochemistry of gneisses associated with ultrahigh pressure eclogites at Shuanghe in the Dabie Mountains - Bin Fu; Yong-Fei Zheng; Zhengrong Wang; Yilin Xiao; Bing Gong; Shuguang Li (Contributions to Mineralogy and Petrology, 1999)